Image fixing method

The use of toner particles with a core-shell structure and specific wax content, combined with a fixing device, addresses the challenge of achieving low-temperature fixability and hot offset resistance while minimizing noise in electrophotographic devices.

JP7608939B2Active Publication Date: 2025-01-07RICOH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021059623
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2021-03-31
Publication Date
2025-01-07
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Existing image fixing methods in electrophotographic devices face challenges in achieving both low-temperature fixability and hot offset resistance while minimizing abnormal noise generation.

Method used

The image fixing method employs toner particles with a core-shell structure containing wax and a binder resin, with a specific wax content of 3% to 10% by mass, and a peak intensity ratio of 0.05 to 0.40 determined by FTIR-ATR, used in conjunction with a fixing device that includes a pressure means and a heater to heat the toner image in a nip portion.

Benefits of technology

This approach achieves both excellent low-temperature fixing properties and hot offset resistance while reducing torque at the nip portion, thereby preventing abnormal noise generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608939000003
    Figure 0007608939000003
  • Figure 0007608939000004
    Figure 0007608939000004
  • Figure 0007608939000005
    Figure 0007608939000005
Patent Text Reader

Abstract

To provide an image fixing method that can achieve both low temperature fixability and hot offset resistance and can prevent the generation of an abnormal noise.SOLUTION: An image fixing method is for fixing a toner image on a recording medium formed with toner in an image fixing device. The toner includes toner particles containing wax and a binder resin and having a core-shell structure. The content of the wax in the toner is 3 mass% to 10 mass%. The intensity ratio (P2850 / P828) of a peak (2,850 cm-1) to a peak (828 cm-1) determined by the FTIR-ATR method is 0.05 or more and 0.40 or less. The image fixing device has pressure means, driving means, fixing means that is arranged opposite to and in contact with the pressure means to form a nip part and is rotated following the rotation of the pressure means, and a heater that heats the fixing means. The image fixing method includes a heating step of heating the toner image with the fixing means at the nip part.SELECTED DRAWING: Figure 2A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an image fixing method. [Background technology]

[0002] In electrophotographic image forming devices such as copiers, facsimiles, and printers, the surface of a photoconductor, which is an electrostatic latent image carrier, is charged by discharging electricity, the charged photoconductor surface is exposed to form an electrostatic latent image, and toner having a polarity opposite to that of the electrostatic latent image formed on the photoconductor surface is supplied and developed to form a toner image on the photoconductor. The toner image formed on the photoconductor is then transferred to an intermediate transfer body and then transferred to a recording medium, or is directly transferred from the photoconductor to the recording medium. The transferred toner image on the recording medium is fixed on the recording medium by applying heat and pressure by a fixing means.

[0003] As the fixing means, for example, a fixing film is an endless belt-like heat-resistant film, suspended and stretched around a driving roller, which is a supporting rotating body for the fixing film, a driven roller, and a heating body that is held and fixed by a heater support provided below the two rollers, and a pressure roller is pressed against the heater support via the fixing film to form a nip portion, in a so-called surf-type fixing device (see Patent Document 1). In the proposed fixing means, a recording medium on which an unfixed toner image has been formed is passed between the fixing film and the pressure roller, and the toner is heated and melted in the nip portion while pressure is applied, thereby fixing the toner image on the recording medium. Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide an image fixing method which can achieve both low-temperature fixability and hot offset resistance and can suppress the generation of abnormal noise. [Means for solving the problem]

[0005] The image fixing method of the present invention as a means for solving the above problems includes: 1. An image fixing method for fixing a toner image formed on a recording medium by an image fixing device, comprising: the toner contains a wax and a binder resin, and contains toner particles having a core-shell structure having a core portion and a shell layer; the content of the wax in the toner is 3% by mass to 10% by mass, Peak (2,850 cm) determined by FTIR-ATR (attenuated total reflection infrared spectroscopy) -1 ) and peak (828cm -1 ) and the intensity ratio (P 2850 / P 828 ) is greater than or equal to 0.05 and less than or equal to 0.40, the image fixing device includes a pressure means, a driving means for driving and rotating the pressure means, a fixing means arranged opposite to the pressure means so as to come into contact with the pressure means to form a nip portion and rotated with the rotation of the pressure means, and a heater for heating the fixing means; The method further comprises a heating step of heating the toner image by the fixing means in the nip portion. Effect of the Invention

[0006] According to the present invention, it is possible to provide an image fixing method which can achieve both excellent low-temperature fixing property and hot offset resistance and can suppress the generation of abnormal noise. [Brief description of the drawings]

[0007] [Figure 1A] FIG. 1A is a diagram showing a schematic example of the shape of a toner used in the image fixing method of the present invention. [Figure 1B] FIG. 1B is a diagram showing a schematic example of the shape of the toner used in the image fixing method of the present invention. [Figure 1C] FIG. 1C is a diagram showing a schematic example of the shape of the toner used in the image fixing method of the present invention. [Figure 2A]FIG. 2A is a schematic diagram (cross-sectional view) showing an example of an image fixing device used in the image fixing method of the present invention. [Figure 2B] FIG. 2B is a schematic diagram (cross-sectional view) showing another example of the image fixing device used in the image fixing method of the present invention. [Figure 2C] FIG. 2C is a schematic diagram (cross-sectional view) showing another example of the image fixing device used in the image fixing method of the present invention. [Figure 2D] FIG. 2D is a schematic diagram (cross-sectional view) showing another example of the image fixing device used in the image fixing method of the present invention. [Diagram 3] FIG. 3 is a diagram showing an example of the developing means in the image forming apparatus of the present invention. [Figure 4] FIG. 4 is a diagram showing the charging characteristics of contact charging. [Figure 5A] FIG. 5A is a diagram showing an example of a roller contact charging device in an image forming apparatus of the present invention. [Figure 5B] FIG. 5B is a diagram showing an example of a brush contact charging device in the image forming apparatus of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] (Image fixing method and image fixing device) The image fixing method of the present invention is a method for fixing a toner image formed on a recording medium by an image fixing device, and includes at least a heating step, preferably a pressure application step, and further includes other steps as necessary. The image fixing device includes a heater, a fixing means, a pressure means, a driving means, and, if necessary, other means. The fixing means is disposed opposite to the pressure means so as to come into contact with the pressure means to form a nip portion (hereinafter, sometimes referred to as a "fixing nip area"), and is rotated with the rotation of the pressure means.

[0009] The present inventors have conducted extensive research in order to provide an image fixing method capable of achieving both excellent low-temperature fixing property and hot offset resistance and suppressing the generation of abnormal noise. In the course of the investigation, the inventors found that a surf-type fixing device having a fixing film suspended and stretched around a driving roller, a driven roller, and a heater supported and fixed by a heater support disposed below the two rollers, and a pressure roller pressed against the heater support via the fixing film to form a nip portion, does not have preheating like a belt-type fixing device, and heats only at the nip portion between the pressure roller and the fixing film, so it is difficult to heat up and is unable to achieve both excellent low-temperature fixing properties and hot offset resistance. In addition, when the pressure roller is driven to rotate and the fixing belt rotates (co-rotates), a large torque (rotation load) is generated, which causes an abnormal noise at the nip portion.

[0010] Therefore, the present inventors conducted further intensive research and found that by using an image fixing device having a pressure means, a driving means for driving and rotating the pressure means, a fixing means arranged opposite to the pressure means so as to contact the pressure means to form a nip portion and rotated with the rotation of the pressure means, and a heater for heating the fixing means, and using a toner containing wax and a binder resin and containing toner particles having a core-shell structure, wherein the wax content and the wax content present in the vicinity of the surface of the toner particles are within specific ranges, and heating the toner image by the fixing means in the nip portion, it is possible to achieve both excellent low-temperature fixability and hot offset resistance, and furthermore, the torque in the nip portion can be reduced, thereby preventing the generation of abnormal noise, thereby completing the present invention.

[0011] <Heating process and heater> The fixing unit can be heated suitably by the heater. The toner image can be heated by the fixing means in the nip portion (fixing nip area), whereby the toner is softened or melted.

[0012] The position of the heater in the image fixing device is not particularly limited as long as it is positioned so as to be able to heat the fixing means, but it is preferable that the heater is positioned so as to be in contact with the pressure means via the fixing means and to heat the fixing nip area via the fixing means.

[0013] The type of the heater is not particularly limited and can be appropriately selected from known heaters, but a plate heater is preferable.

[0014] The heating temperature in the heating step is not particularly limited and can be appropriately selected depending on the intended fixing temperature, etc. The upper limit fixing temperature is preferably 170° C. or higher. The lower limit fixing temperature is preferably 140° C. or lower, more preferably 130° C. or lower.

[0015] <Pressing Step, Fixing Unit, Pressing Unit, and Driving Unit> The pressure application step can be suitably performed by the fixing unit, the pressure application unit, and the driving unit. The pressurizing step is a step of pressurizing the toner image. Specifically, when the recording medium having the toner image passes through the fixing nip area formed by the fixing means and the pressurizing means, the toner image is pressed against the fixing means by the pressurizing means. The image fixing method including the pressurizing step is preferable in that the toner can be spread and the fixing speed can be increased. The pressurizing step is preferably carried out simultaneously with the heating step.

[0016] The pressurizing time in the pressurizing step is not particularly limited and can be appropriately selected depending on the purpose.

[0017] <<Pressure means>> The shape of the pressure means is not particularly limited, but is preferably in the form of a roller. The configuration of the pressure applying means is not particularly limited and can be appropriately selected from known pressure applying means, for example, one having a core bar, an elastic layer formed on the surface of the core bar, and a release layer formed on the outside of the elastic layer.

[0018] The material for the elastic layer is not particularly limited and can be appropriately selected depending on the purpose. For example, silicone rubber is available.

[0019] The material of the release layer is not particularly limited and can be appropriately selected depending on the purpose. For example, fluorine resin and the like can be used.

[0020] The size of the pressure means (diameter in the case of a roller), the thickness of the elastic layer, and the thickness of the release layer are not particularly limited and can be appropriately selected depending on the purpose.

[0021] The pressure means is driven to rotate by the drive means, preferably rotating counterclockwise, and is pressed against the fixing nip region with a total contact pressure of 4 kg to 10 kg.

[0022] The pressure applied in the pressurizing step is not particularly limited, but the surface pressure (roller load / contact area) applied between the fixing unit and the pressurizing unit is preferably 1.5×10 5 The toner used in the image fixing method of the present invention can be fixed sufficiently even at low temperatures, so that the surface pressure is preferably 1.5×10 Pa or less. 5 This makes it possible to fix the toner even at a low surface pressure of less than 1 Pa. In addition, the low surface pressure prevents the toner image on the recording medium from being crushed or disturbed, making it possible to output high-definition images.

[0023] <<Fixing method>> The fixing means is disposed opposite to the pressure means so as to contact the pressure means to form a nip portion (fixing nip area) and is rotated with the rotation of the pressure means. Since the fixing means is rotated with the rotation of the pressure means, no drive means for the fixing means is required.

[0024] The configuration of the fixing means is not particularly limited and can be appropriately selected from known fixing means, but it is preferable that the fixing means has a cylindrical body and an endless fixing film (hereinafter sometimes referred to as a "fixing belt") arranged on the surface of the cylindrical body. It is also preferable that the heater is disposed inside the cylindrical body, that is, on the surface opposite to the surface in contact with the pressure means in the fixing nip region.

[0025] The material of the cylindrical substrate is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include heat-resistant resins such as polyimide (PI) and polyether ether ketone (PEEK), metals such as nickel (Ni) and stainless steel (SUS), etc. These may be used alone or in combination of two or more.

[0026] The configuration of the fixing belt is not particularly limited and can be appropriately selected depending on the purpose, but it is preferable that the fixing belt has a surface layer (release layer) and an elastic layer disposed between the substrate (base layer) and the surface layer.

[0027] The material of the surface layer (release layer) is not particularly limited, but is preferably one having excellent heat resistance, releasability, and durability, such as polyimide (PI), polyetherimide (PEI), polyether sulfide (PES), tetrafluoroethylene perfluoroalkyl vinyl ether copolymer resin (PFA), tetrafluoroethylene resin (PTFE), etc. The surface layer may be a single layer film made of the resin, or a composite layer film.

[0028] The average thickness of the surface layer (release layer) is not particularly limited and can be appropriately selected depending on the purpose, but is usually preferably about 5 μm to 50 μm. In this specification, the average thickness of the surface layer (release layer) can be calculated from a scanning electron microscope (SEM) image of a cut surface perpendicular to the length direction of the fixing belt, and is the average thickness of 10 points randomly selected in the length direction and width direction of the fixing belt.

[0029] The material of the elastic layer is not particularly limited and can be appropriately selected from materials having releasability, for example, fluorine-based resins such as tetrafluoroethylene perfluoroalkyl vinyl ether copolymer resin (PFA) and tetrafluoroethylene resin (PTFE), etc. These may be used alone or in combination of two or more.

[0030] The average thickness of the elastic layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 50 μm to 5,000 μm. In this specification, the average thickness of the elastic layer can be calculated from a scanning electron microscope (SEM) image of a cut surface perpendicular to the length direction of the fixing belt, and is the average thickness of 10 points randomly selected in the length direction and width direction of the fixing belt.

[0031] <<Drive means>> The driving means is a means for driving and rotating the pressure means.

[0032] The position of the driving means in the image fixing device is not particularly limited as long as it is disposed so as to be able to drive the pressure means, but it is preferable that the driving means be disposed inside the pressure means.

[0033] The rotational drive speed of the pressure means by the drive means is not particularly limited, but it is preferably adjusted to a speed at which the speeds of the recording medium and the pressure means are equal in the fixing nip area.

[0034] The configuration of the image fixing device and the image fixing method will be specifically described below with reference to the drawings. An example of an image fixing device of the present invention is shown in Fig. 2A. The image fixing device is a so-called surf fixing device that fixes an image by rotating a fixing belt. As shown in FIG. 2A, the image fixing device 109 according to this embodiment includes a fixing belt 1020 consisting of an endless belt, a pressure roller 1021 as an opposing member that contacts the outer peripheral surface of the fixing belt 1020 to form a fixing nip area N, a heater 1022 as a heating member that heats the fixing belt 1020, a heater folder 1023 as a holding member that holds the heater 1022, a stay 1024 as a support member that supports the heater folder 1023, and a thermistor 1025 as a temperature detection means that detects the temperature of the fixing belt 1020.

[0035] The fixing belt 1020 has a cylindrical substrate made of polyimide (PI) having an outer diameter of 25 mm and a thickness of 40 μm to 120 μm, for example. A release layer made of fluororesin such as PFA or PTFE and having an average thickness of 5 μm to 50 μm is formed on the outermost surface of the fixing belt 1020 in order to increase durability and ensure releasability. An elastic layer made of rubber or the like having a thickness of 50 μm to 500 μm may be provided between the substrate and the release layer (surface layer). The substrate of the fixing belt 1020 is not limited to polyimide, and may be a heat-resistant resin such as PEEK or a metal substrate such as nickel (Ni) or stainless steel (SUS). The inner peripheral surface of the fixing belt 1020 may be coated with polyimide, PTFE, or the like as a sliding layer.

[0036] The pressure roller 1021 has an outer diameter of, for example, 25 mm and is composed of a solid iron core 1021a, an elastic layer 1021b formed on the surface of the core 1021a, and a release layer 1021c formed on the outside of the elastic layer 1021b. The elastic layer 1021b is made of silicone rubber and has a thickness of, for example, 3.5 mm. In order to improve the releasability of the surface of the elastic layer 1021b, it is preferable to form a release layer 1021c made of a fluororesin layer having a thickness of, for example, about 40 μm.

[0037] The pressure roller 1021 is urged toward the fixing belt 1020 by the urging means, so that the pressure roller 1021 is pressed against the heater 1022 via the fixing belt 1020. As a result, a fixing nip region N is formed between the fixing belt 1020 and the pressure roller 1021. The pressure roller 1021 is configured to be rotationally driven by a driving means, and when the pressure roller 1021 rotates in the direction of the arrow in FIG. 2A, the fixing belt 1020 rotates accordingly (rotates together). This rotational drive speed is adjusted to a speed at which the speeds of the recording medium P and the fixing belt 1020 are equal in the fixing nip region N where the pressure roller 1021 and the fixing belt 1020 come into contact with each other.

[0038] The heater 1022 is a plate-shaped heating member provided longitudinally across the width of the fixing belt 1020, and is composed of a plate-shaped base material 1030, a resistance heating element 1031 provided on the base material 1030, and an insulating layer 1032 that covers the resistance heating element 1031. Such a plate-shaped heater is made of, for example, Ag / Pd, Ta 2 The heater 1022 is formed by applying an electric resistance material such as N in a line or band shape by screen printing or the like. The heater 1022 is in contact with the inner circumferential surface of the fixing belt 1020 on the insulating layer 1032 side, and heat generated from the resistance heating element 1031 is transferred to the fixing belt 1020 via the insulating layer 1032. In this embodiment, the resistance heating element 1031 and the insulating layer 1032 are provided on the fixing belt 1020 side (fixing nip region N side) of the base material 1030, but conversely, the resistance heating element 1031 and the insulating layer 1032 may be provided on the heater folder 1023 side of the base material 1030. In that case, since the heat of the resistance heating element 1031 is transferred to the fixing belt 1020 via the base material 1030, it is preferable that the base material 1030 is made of a material with high thermal conductivity such as aluminum nitride. Furthermore, by forming the base material 1030 from a material with good thermal conductivity, even if the resistance heating element 1031 is disposed on the opposite side of the base material 1030 from the fixing belt 1020, it is possible to sufficiently heat the fixing belt 1020.

[0039] The heater folder 1023 and the stay 1024 are disposed on the inner circumferential side of the fixing belt 1020. The stay 1024 is made of a metal channel material, and both ends thereof are supported by both side plates of the image fixing device 109. Since the heater folder 1023 and the heater 1022 held thereby are supported by the stay 1024, when the pressure roller 1021 is pressed against the fixing belt 1020, the heater 1022 reliably receives the pressing force of the pressure roller 1021, and the fixing nip area N is stably formed.

[0040] The heater folder 1023 is preferably made of a heat-resistant material since it is likely to become hot due to the heat of the heater 1022. For example, when the heater folder 1023 is made of a heat-resistant resin with low thermal conductivity such as liquid crystal polymer (LCP), heat transfer from the heater 1022 to the heater folder 1023 is suppressed, and the fixing belt 1020 can be heated efficiently. In addition, in order to reduce the contact area of ​​the heater folder 1023 with the heater 1022 and reduce the amount of heat transferred from the heater 1022 to the heater folder 1023, the heater folder 1023 contacts the base material 1030 of the heater 1022 via a protrusion 1023a. Furthermore, as in this embodiment, by contacting the protrusion 1023a of the heater holder 1023 with the substrate 1030 other than the back side of the portion where the resistance heating element 1031 is arranged, i.e., avoiding the portion of the substrate 1030 where the temperature is likely to be high, the amount of heat transferred to the heater holder 1023 can be further reduced and the fixing belt 1020 can be heated efficiently. In addition, the temperature information of the fixing belt 1020 detected by the thermistor 1025 is sent to a control means (not shown), and the control means controls the amount of power supplied to the heater 1022, so that the heater 1022 is controlled to a predetermined temperature. The control means means a microcomputer including a CPU, a ROM, a RAM, an I / O interface, etc. However, when paper is being passed, the temperature of the fixing belt 1020 is controlled to a desired temperature by appropriately inputting additional power in consideration of the amount of heat dissipated by the paper being passed, in addition to the temperature information.

[0041] The heater folder 1023 is provided with guide portions 1026 that guide the fixing belt 1020. The guide portions 1026 are provided on the upstream side (below the heater 1022 in FIG. 2A) and downstream side (upper side of the heater 1022 in FIG. 2A) of the belt rotation direction of the heater 1022.

[0042] In the image fixing device 109, when a printing operation is started, the pressure roller 1021 is rotated and the fixing belt 1020 starts to rotate. At this time, the inner circumferential surface of the fixing belt 1020 contacts and is guided by the belt facing surface 1260 of the guide portion 1026, so that the fixing belt 1020 rotates stably and smoothly. In addition, the fixing belt 1020 is heated by supplying power to the resistance heating element 1031 of the heater 1022. Then, in a state where the temperature of the fixing belt 1020 has reached a predetermined target temperature (fixing temperature), as shown in FIG. 2A, the recording medium P carrying an unfixed toner image is conveyed between the fixing belt 1020 and the pressure roller 1021 (fixing nip region N), so that the unfixed toner image is heated and pressurized to be fixed to the recording medium P.

[0043] The image fixing device may be, for example, an image fixing device as shown in Figures 2B to 2D in addition to the fixing device shown in Figure 2A. The configuration of each image fixing device shown in Figures 2B to 2D will be briefly described below.

[0044] First, the image fixing device 109 shown in FIG. 2B is configured such that a pressure roller 1044 is disposed on the opposite side of the fixing belt 1020 to the pressure roller 1021 side, and the fixing belt 1020 is sandwiched and heated by the pressure roller 1044 and the heater 1022. On the other hand, on the pressure roller 1021 side, a nip forming member 1045 is disposed on the inner periphery of the fixing belt 1020. The nip forming member 1045 is supported by a stay 1024, and the fixing belt 1020 is sandwiched between the nip forming member 1045 and the pressure roller 1021 to form a fixing nip region N. In addition, the nip forming member 1045 is provided with a guide portion 1026 that guides the fixing belt 1020.

[0045] 2C, the above-mentioned pressure roller 1044 is omitted, and in order to ensure the circumferential contact length between the fixing belt 1020 and the heater 1022, the heater 1022 is formed in an arc shape in accordance with the curvature of the fixing belt 1020. The rest of the configuration is the same as that of the image fixing device 109 shown in FIG. 2B.

[0046] Finally, in the image fixing device 109 shown in FIG. 2D, in addition to the fixing belt 1020, a pressure belt 1046 is provided, and a heating nip (first fixing nip area) N1 and a fixing nip (second fixing nip area) N2 are separately configured. That is, a nip forming member 1045 and a stay 1047 are arranged on the opposite side of the fixing belt 1020 side with respect to the pressure roller 1021, and the pressure belt 1046 is rotatably arranged so as to include the nip forming member 1045 and the stay 1047. Then, the recording medium P is passed through the fixing nip area N2 between the pressure belt 1046 and the pressure roller 1021 and heat and pressure are applied to fix the image. The other configurations are the same as those of the image fixing device 109 shown in FIG. 2A.

[0047] <<Toner image>> The toner image is formed on the recording medium using the toner. The toner image is formed, for example, by a process including an electrostatic latent image forming process and a developing process in a conventionally known image forming method. The film can be fabricated by a transfer process.

[0048] <<<Toner>>> The toner contains a wax and a binder resin, and preferably further contains a shell layer material, and further contains other components as necessary. The toner may be a transparent toner or may contain a colorant. The toner is a toner containing toner particles having a core-shell structure having a core and a shell layer (hereinafter, sometimes referred to as "capsule toner"). The shell layer is disposed on the surface of the core, and the shell layer may cover the entire surface of the core, or may cover only a part of the surface. An example of a shell layer that covers only a part of the core is one in which the shell layer is present on the surface of the core in an island shape. The wax and the binder resin are preferably contained in the core particle, but may be contained in the shell layer.

[0049] -wax- The content of the wax in the toner (hereinafter sometimes referred to as "total amount of wax") is 3% by mass to 10% by mass, and preferably 3% by mass to 5% by mass. If the content of the wax in the toner is less than 3% by mass, sufficient releasability is not obtained during fixing, and hot offset resistance is reduced. If the content of the wax in the toner exceeds 10% by mass, blocking resistance is reduced, and color images lose gloss after fixing.

[0050] Peak (2,850 cm) determined by FTIR-ATR (attenuated total reflection infrared spectroscopy) -1 ) and peak (828cm -1 ) and the intensity ratio (P 2850 / P 828 ) is from 0.05 to 0.40, and from the viewpoints of achieving a balance between hot offset resistance during fixing, charging properties, developability, blocking resistance, and the like, and suppressing the generation of abnormal noise, it is more preferably from 0.05 to 0.30. The intensity ratio (P 2850 / P 828 ) represents the relative amount of wax near the toner surface. Note that, based on the measurement principle of the FTIR-ATR method, the vicinity of the toner surface refers to a depth of about 0.3 μm from the toner surface. The intensity ratio (P 2850 / P 828 If the intensity ratio (P) is less than 0.05, abnormal noise occurs and sufficient releasability cannot be obtained during fixing.2850 / P 828 When the ratio exceeds 0.40, the wax is exposed on the outermost surface of the toner particle.

[0051] The infrared absorption spectrum obtained by the FTIR-ATR (attenuated total reflection infrared spectroscopy) method can be measured by an appropriately selected method. For example, a method is available in which 3 g of a sample toner is pressed for 1 minute with an automatic pellet molding machine (Type M No.50 BRP-E, manufactured by MAEKAWA TESTING MACHINE CO.) under a load of 6 t to prepare a pellet having a diameter of 40 mm (thickness of about 2 mm), and the toner pellet is measured by the ATR method (attenuated total reflection method) using a Fourier transform infrared (FT-IR) spectroscopic analysis measuring device (Avatar370, manufactured by ThermoElectron). In this specification, 2,850 cm -1 Peak (height of baseline: 2,830 cm -1 ~2,870cm -1 ) to P 2850 and 828cm -1 Peak height (baseline) 743cm -1 ~890cm -1 ) to P 828 The intensity ratio (P 2850 / P 828 ) is calculated. Here, the baseline height is 2,830 cm -1 ~2,870cm -1 2,850 cm -1 The peak is 2,830 cm -1 ~2,870cm -1 Peaks in the range of 2,850 cm -1 The peak is 743cm. -1 ~890cm -1 That is 828cm -1 The peak is 743cm -1 ~890cm -1 The peak in the range of 828 cm -1 This means that the peak P 2850is a wax peak, and was set by extracting characteristic peaks from the full-range infrared absorption spectrum obtained by the FTIR-ATR method for the wax alone. 828 is a resin peak, and the detected structure is presumed to be a peak of COC antisymmetric stretching of aliphatic-aromatic ether.

[0052] In order to improve the hot offset resistance in the fixing step, it is preferable that the wax is present near the surface of the toner particles. However, if the wax is present on the outermost surface of the toner particles, it will hinder the uniform charging of the toner. In addition, the wax will exhibit cohesiveness and hinder the flowability of the toner particles. Even if external additives such as inorganic fine particles are added to improve the chargeability and flowability of the toner, these external additives will be buried by the wax present on the surface of the toner particles, and the chargeability and flowability will not be obtained. Furthermore, during long-term use, the wax will migrate to the surface of the magnetic carrier, causing a decrease in chargeability and a decrease in the life of the developer, or migrate onto the photoconductor to cause filming. In addition, if the wax present on the surface of the toner particles melts due to the atmospheric temperature during toner storage, toner blocking will occur, and storage stability will decrease. On the other hand, if the wax is present in the interior of the toner particles in an aggregated state, sufficient releasability will not be obtained, and hot offset resistance will decrease. Therefore, the toner used in the image fixing method is one in which at least a part of the wax is present in a so-called dispersed state as a plurality of independent wax dispersion particles contained in the toner, and by determining the content of the wax and the content (relative amount) of the wax present in the vicinity of the surface of the toner particles, it was possible to satisfy both the chargeability, fluidity, and releasability. In addition, by setting the total amount of wax and the content (relative amount) of the wax present in the vicinity of the surface of the toner particles to a specific amount, the wax moves to the nip portion for the first time, the torque at the nip portion is reduced, and as a result, it was found that the generation of abnormal noise is reduced as the content (relative amount) of the wax present in the vicinity of the surface of the toner particles increases.

[0053] The dispersion state of the wax in the toner used in the image fixing method can be specified by the total amount of wax in the toner particles and the relative amount of wax in the vicinity of the surface of the toner particles, by the following measurement.

[0054] The total amount of wax in the toner particles is determined by a DSC (differential scanning calorimeter) method. Specifically, a toner sample and a single wax sample (standard wax) are measured using the following measurement device and measurement conditions, and the total amount of wax is determined from the amount of heat absorbed by the wax obtained from each measurement, using a ratio calculated from the following formula 1. The amount of heat absorbed by the wax is determined from the DSC curve at the second temperature rise. The total amount of wax determined by the DSC method has little variation, so it can be determined in a single measurement. [Measurement equipment and conditions] Measurement equipment: DSC equipment (DSC60, manufactured by Shimadzu Corporation) Sample size: Approx. 5 mg Heating temperature: 10℃ / min Measurement range: Room temperature (23±2℃) to 150℃ Measurement environment: Nitrogen gas atmosphere

[0055] The total amount of wax is calculated by the following formula 1. Total amount of wax (mass%) = (amount of heat absorbed by the wax in the toner sample (J / g)) × 100 / (amount of heat absorbed by the wax sample alone (J / g)) Equation 1 Here, the "single wax sample" in formula 1 is Nissan Electol (registered trademark) WEP-3, an ester wax (acid value 0.1 mg KOH / g, hydroxyl value 4.0 mg KOH / g or less, loss on drying 0.1% to 0.3%, hue (Gardner) 1, clear melting point 73.2°C, manufactured by NOF Corporation). By the above analysis, even in the case where the wax flows out during the toner manufacturing process and all of the charged wax is not contained in the toner, the total amount of wax in the toner particles can be effectively determined.

[0056] The type of wax is not particularly limited, and conventionally known waxes can be used, for example, low molecular weight polyolefin waxes such as low molecular weight polyethylene and low molecular weight polypropylene; synthetic hydrocarbon waxes such as Fischer-Tropsch wax; natural waxes such as beeswax, carnauba wax, candelilla wax, rice wax, and montan wax; petroleum waxes such as paraffin wax and microcrystalline wax; fatty acid waxes such as stearic acid, palmitic acid, and myristic acid, or metal salts of the higher fatty acid, and higher fatty acid amides; ester waxes such as synthetic ester wax; or various modified waxes thereof. These may be used alone or in combination of two or more. Among these waxes, carnauba wax and its modified wax, rice wax, and ester waxes are preferred, and ester waxes are particularly preferred.

[0057] -Binding resin- The binder resin is not particularly limited and may be a conventionally known one, but it is preferable to use a polyester resin. Examples of the polyester resin include modified polyester and unmodified polyester. These may be used alone or in combination of two or more.

[0058] --Modified polyester-- The modified polyester (i) refers to a polyester resin in which a bonding group other than an ester bond is present, or in which a resin component having a different structure is bonded to the polyester resin by a covalent bond, an ionic bond, etc. Specifically, it refers to a polyester resin in which a functional group such as a carboxylic acid group or an isocyanate group that reacts with a hydroxyl group is introduced into the polyester terminal, and the polyester terminal is further modified by reacting with an active hydrogen-containing compound.

[0059] The modified polyester (i) may, for example, be a polyester modified with a urea bond (hereinafter sometimes referred to as "urea-modified polyester") obtained by reacting a polyester prepolymer (A) having an isocyanate group with an amine (B).

[0060] The polyester prepolymer (A) having an isocyanate group may be, for example, a polycondensate of a polyhydric alcohol (PO) and a polycarboxylic acid (PC), which is a polyester having an active hydrogen group, and is further reacted with a polyisocyanate compound (PIC). Examples of the active hydrogen group of the polyester include a hydroxyl group (alcoholic hydroxyl group and phenolic hydroxyl group), an amino group, a carboxyl group, and a mercapto group. Among these, the active hydrogen group of the polyester is preferably an alcoholic hydroxyl group.

[0061] The polyhydric alcohol compound (PO) is not particularly limited, and examples thereof include dihydric alcohols (DIO) and trihydric or higher polyhydric alcohols (TO). Preferably, DIO is used alone or a mixture of DIO with a small amount of TO.

[0062] Examples of the dihydric alcohol (DIO) include alkylene glycols (ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,6-hexanediol, etc.); alkylene ether glycols (diethylene glycol, triethylene glycol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene ether glycol, etc.); alicyclic diols (1,4-cyclohexanedimethanol, hydrogenated bisphenol A, etc.); bisphenols (bisphenol A, bisphenol F, bisphenol S, etc.); alkylene oxide (ethylene oxide, propylene oxide, butylene oxide, etc.) adducts of the alicyclic diols; and alkylene oxide (ethylene oxide, propylene oxide, butylene oxide, etc.) adducts of the bisphenols. These may be used alone or in combination of two or more. Among these, preferred are alkylene glycols having 2 to 12 carbon atoms and alkylene oxide adducts of bisphenols, and particularly preferred are alkylene oxide adducts of bisphenols and their combined use with alkylene glycols having 2 to 12 carbon atoms.

[0063] Examples of the trihydric or higher polyhydric alcohol (TO) include trihydric to octahydric or higher polyhydric aliphatic alcohols (glycerin, trimethylolethane, trimethylolpropane, pentaerythritol, sorbitol, etc.); trihydric or higher phenols (trisphenol PA, phenol novolac, cresol novolac, etc.); alkylene oxide adducts of the trihydric or higher polyphenols. These may be used alone or in combination of two or more.

[0064] The polycarboxylic acid (PC) is not particularly limited, and examples thereof include dicarboxylic acids (DIC) and tricarboxylic or higher polycarboxylic acids (TC). Of these, (DIC) alone and a mixture of (DIC) and a small amount of (TC) are preferred.

[0065] The divalent carboxylic acid (DIC) may include alkylene dicarboxylic acids (succinic acid, adipic acid, sebacic acid, etc.), alkenylene dicarboxylic acids (maleic acid, fumaric acid, etc.), aromatic dicarboxylic acids (phthalic acid, isophthalic acid, terephthalic acid, naphthalene dicarboxylic acid, etc.), etc. Among these, preferred are alkenylene dicarboxylic acids having 4 to 20 carbon atoms and aromatic dicarboxylic acids having 8 to 20 carbon atoms.

[0066] Examples of the trivalent or higher polyvalent carboxylic acid (TC) include aromatic polyvalent carboxylic acids having 9 to 20 carbon atoms (trimellitic acid, pyromellitic acid, etc.). The polyvalent carboxylic acid (PC) may be one obtained by reacting the acid anhydride or lower alkyl ester (methyl ester, ethyl ester, isopropyl ester, etc.) of the above-mentioned compounds with a polyhydric alcohol (PO).

[0067] The ratio of the polyhydric alcohol (PO) to the polycarboxylic acid (PC) is not particularly limited, but the equivalent ratio ([OH] / [COOH]) of the hydroxyl group [OH] to the carboxyl group [COOH] is usually 2 / 1 to 1 / 1, preferably 1.5 / 1 to 1 / 1, and more preferably 1.3 / 1 to 1.02 / 1.

[0068] The polyisocyanate compound (PIC) is not particularly limited, and examples thereof include aliphatic polyisocyanates (tetramethylene diisocyanate, hexamethylene diisocyanate, 2,6-diisocyanatomethylcaproate, etc.); alicyclic polyisocyanates (isophorone diisocyanate, cyclohexylmethane diisocyanate, etc.); aromatic diisocyanates (tolylene diisocyanate, diphenylmethane diisocyanate, etc.); aromatic aliphatic diisocyanates (α,α,α',α'-tetramethylxylylene diisocyanate, etc.); isocyanates; the alicyclic polyisocyanates blocked with phenol derivatives, oximes, caprolactam, etc.; and combinations of two or more of these.

[0069] The ratio of the polyisocyanate compound (PIC), expressed as the equivalent ratio ([NCO] / [OH]) of the isocyanate group [NCO] to the hydroxyl group [OH] of the polyester having a hydroxyl group, is usually 5 / 1 to 1 / 1, preferably 4 / 1 to 1.2 / 1, and more preferably 2.5 / 1 to 1.5 / 1.

[0070] The content of the polyisocyanate compound (PIC) in the polyester prepolymer (A) having an isocyanate group is usually 0.5% by mass to 40% by mass, preferably 1% by mass to 30% by mass, and more preferably 2% by mass to 20% by mass.

[0071] Next, the amines (B) to be reacted with the polyester prepolymer (A) are not particularly limited, and examples thereof include divalent amine compounds (B1), trivalent or higher polyvalent amine compounds (B2), amino alcohols (B3), amino mercaptans (B4), amino acids (B5), and compounds (B6) in which the amino groups of the above (B1) to (B5) have been blocked. These may be used alone or in combination of two or more.

[0072] Examples of the divalent amine compound (B1) include aromatic diamines (phenylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenylmethane, etc.); alicyclic diamines (4,4'-diamino-3,3'-dimethyldicyclohexylmethane, diaminecyclohexane, isophoronediamine, etc.); and aliphatic diamines (ethylenediamine, tetramethylenediamine, hexamethylenediamine, etc.).

[0073] Examples of the trivalent or higher polyvalent amine compound (B2) include diethylenetriamine and triethylenetetramine.

[0074] Examples of the amino alcohol (B3) include ethanolamine and hydroxyethylaniline.

[0075] Examples of the amino mercaptan (B4) include aminoethyl mercaptan and aminopropyl mercaptan.

[0076] Examples of the amino acid (B5) include aminopropionic acid and aminocaproic acid.

[0077] Examples of compounds (B6) obtained by blocking the amino group of the above (B1) to (B5) include ketimine compounds obtained from the above amines (B1) to (B5) and ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, etc.) and oxazolidine compounds.

[0078] Among these, preferred among the amines (B) are the above-mentioned (B1) and a mixture of the above-mentioned (B1) with a small amount of the above-mentioned (B2).

[0079] The ratio of the amines (B), expressed as the equivalent ratio ([NCO] / [NHx]) of the isocyanate group [NCO] in the polyester prepolymer (A) having an isocyanate group to the amino group [NHx] in the amines (B), is usually 1 / 2 to 2 / 1, preferably 1.5 / 1 to 1 / 1.5, and more preferably 1.2 / 1 to 1 / 1.2.

[0080] The urea-modified polyester may contain a urethane bond together with the urea bond. The molar ratio of the content of the urea bond to the content of the urethane bond is usually 100 / 0 to 10 / 90, preferably 80 / 20 to 20 / 80, and more preferably 60 / 40 to 30 / 70.

[0081] The modified polyester (i) is produced by a one-shot method, a prepolymer method, etc. The weight average molecular weight of the modified polyester (i) is usually 10,000 or more, preferably 20,000 to 10 million, and more preferably 30,000 to 1 million. In this case, the peak molecular weight is preferably 1,000 to 10,000.

[0082] The number average molecular weight of the modified polyester (i) is not particularly limited when a non-modified polyester (ii) described below is used, and may be any number average molecular weight that is easy to obtain to obtain the weight average molecular weight. When the modified polyester (i) is used alone, the number average molecular weight is usually 20,000 or less, preferably 1,000 to 10,000, and more preferably 2,000 to 8,000.

[0083] In the crosslinking and / or elongation reaction between the polyester prepolymer (A) and the amines (B) to obtain the modified polyester (i), a reaction terminator may be used as necessary to adjust the molecular weight of the resulting urea-modified polyester. Examples of the reaction terminator include monoamines (diethylamine, dibutylamine, butylamine, laurylamine, etc.) and blocked monoamines (ketimine compounds).

[0084] --Unmodified polyester-- In the binder resin, the modified polyester (i) may be used alone, and the unmodified polyester (ii) may be contained together with the modified polyester (i) as a binder resin component. The combined use of the modified polyester (i) and the unmodified polyester (ii) is preferable in that it improves low-temperature fixability and glossiness when used in a full-color device, compared with the case where the modified polyester (i) is used alone.

[0085] The unmodified polyester (ii) may be a polycondensate of a polyhydric alcohol (PO) and a polycarboxylic acid (PC) similar to the modified polyester (i), and the preferred ones are also similar to the modified polyester (i). The unmodified polyester (ii) may be not only an unmodified polyester, but also one modified with a chemical bond other than a urea bond, for example, one modified with a urethane bond.

[0086] The modified polyester (i) and the unmodified polyester (ii) are preferably at least partially compatible with each other in terms of low-temperature fixability and hot offset resistance. Therefore, the modified polyester (i) and the unmodified polyester (ii) are preferably similar in composition. When the unmodified polyester (ii) is contained, the weight ratio of the modified polyester (i) to the unmodified polyester (ii) is usually 5 / 95 to 80 / 20, preferably 5 / 95 to 30 / 70, more preferably 5 / 95 to 25 / 75, and particularly preferably 7 / 93 to 20 / 80.

[0087] The peak molecular weight of the unmodified polyester (ii) is usually from 1,000 to 10,000, preferably from 2,000 to 8,000, and more preferably from 2,000 to 5,000.

[0088] The unmodified polyester (ii) preferably has a hydroxyl value of 5 mgKOH / g or more, more preferably 10 mgKOH / g to 120 mgKOH / g, and particularly preferably 20 mgKOH / g to 80 mgKOH / g, and preferably has an acid value of 1 mgKOH / g to 5 mgKOH / g, and more preferably 2 mgKOH / g to 4 mgKOH / g.

[0089] The glass transition point (Tg) of the binder resin is usually 35°C to 70°C, and preferably 55°C to 65°C.

[0090] The binder resin can be produced by the following method. The polyhydric alcohol (PO) and the polycarboxylic acid (PC) are heated to 150°C to 280°C in the presence of a known esterification catalyst such as tetrabutoxy titanate or dibutyltin oxide, and the water generated is distilled off under reduced pressure as necessary to obtain a polyester having hydroxyl groups. The polyester is then reacted with the polyisocyanate compound (PIC) at 40°C to 140°C to obtain a prepolymer (A) having isocyanate groups. The prepolymer (A) having isocyanate groups is then reacted with the amines (B) at 0°C to 140°C to obtain a urea-modified polyester as the modified polyester (i).

[0091] When reacting the polyisocyanate compound (PIC) and when reacting the prepolymer (A) having an isocyanate group with the amines (B), a solvent may be used if necessary. Examples of the solvent that can be used in the reaction include solvents that are inactive to the polyvalent isocyanate compound (PIC). Specific examples of the solvent include aromatic solvents (toluene, xylene, etc.); ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, etc.); esters (ethyl acetate, etc.); amides (dimethylformamide, dimethylacetamide, etc.), and ethers (tetrahydrofuran, etc.).

[0092] When the unmodified polyester (ii) is used in combination as the binder resin, the unmodified polyester (ii) is produced in the same manner as in the case of the polyester having a hydroxyl group, and is dissolved in the solution obtained after the reaction of the modified polyester (i) and mixed.

[0093] -Shell layer material- The material for the shell layer is not particularly limited and can be appropriately selected from materials used for the shell layer of known toners, but preferably contains a polymer-based protective colloid. The polymer protective colloid is not particularly limited, and examples thereof include acids such as acrylic acid, methacrylic acid, α-cyanoacrylic acid, α-cyanomethacrylic acid, itaconic acid, crotonic acid, fumaric acid, maleic acid, and maleic anhydride; (meth)acrylic monomers containing a hydroxyl group such as β-hydroxyethyl acrylate, β-hydroxyethyl methacrylate, β-hydroxypropyl acrylate, β-hydroxypropyl methacrylate, γ-hydroxypropyl acrylate, γ-hydroxypropyl methacrylate, 3-chloro 2-hydroxypropyl acrylate, 3-chloro 2-hydroxypropyl methacrylate, diethylene glycol monoacrylate, diethylene glycol monomethacrylate, glycerin monoacrylate, glycerin monomethacrylate, N-methylol acrylamide, and N-methylol methacrylamide; vinyl alcohols such as vinyl methyl ether, vinyl ethyl ether, and vinyl propyl ether, or ethers with vinyl alcohol. esters of compounds containing vinyl alcohol and a carboxyl group, such as vinyl acetate, vinyl propionate, and vinyl butyrate; acrylamide, methacrylamide, diacetone acrylamide, or methylol compounds thereof; acid chlorides, such as acrylic acid chloride and methacrylic acid chloride; homopolymers or copolymers of nitrogen-containing compounds, such as vinylpyridine, vinylpyrrolidone, vinylimidazole, and ethyleneimine, or compounds having a heterocyclic ring thereof; polyoxyethylene-based compounds, such as polyoxyethylene, polyoxypropylene, polyoxyethylene alkylamines, polyoxypropylene alkylamines, polyoxyethylene alkylamides, polyoxypropylene alkylamides, polyoxyethylene nonylphenyl ether, polyoxyethylene lauryl phenyl ether, polyoxyethylene stearyl phenyl ester, and polyoxyethylene nonyl phenyl ester; and celluloses, such as methyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose. The polymer-based protective colloid can also act as a dispersant that stabilizes the dispersion of resin particles and inorganic compounds in an aqueous medium during the production of the toner.

[0094] -Other ingredients- The other components in the toner are not particularly limited and can be appropriately selected from conventionally known components used in toners. Examples of the other components include colorants, charge control agents, and external additives.

[0095] --Coloring agent-- The colorant is not particularly limited, and all known dyes and pigments can be used. For example, carbon black, nigrosine dye, iron black, naphthol yellow S, Hansa yellow (10G, 5G, G), cadmium yellow, yellow iron oxide, yellow ocher, yellow lead, titanium yellow, polyazo yellow, oil yellow, Hansa yellow (GR, A, RN, R), pigment yellow L, benzidine yellow (G, GR), permanent yellow (NCG), Balkan fast yellow (5G, R), tartrazine lake, quinoline yellow lake, anthrazan yellow, -BGL, Isoindolinone Yellow, Bengala, Red Lead, Cinnabar, Cadmium Red, Cadmium Mercury Red, Antimony Vermilion, Permanent Red 4R, Para Red, Phaysee Red, Parachlor Orthonitroaniline Red, Lithol Fast Scarlet G, Brilliant Fast Scarlet, Brilliant Kanmin BS, Permanent Red (F2R, F4R, FRL, FRLL, F4RH), Fast Scarlet VD, Belkan Fast Rubin B, Brilliant Scarlet G, Lithol Rubin GX, Permanent Red F5R, Brilliant Carmine 6B, Pigment Scarlet 3B, Bordeaux 5B, Toluidine Maroon, Permanent Bordeaux F2K, Helio Bordeaux BL, Bordeaux 10B, Bon Maroon Light, Bon Maroon Medium, Eosin Lake, Rhodamine Lake B, Rhodamine Lake Y, Alizarin Lake, Thioindigo Red B, Thioindigo Maroon, Oil Red, Quinacridone Red, Pyrazolone Red, Polyazo Red, Chrome Vermilion, Benzidine Orange, Perinone Orange, Oil Orange, Cobalt Blue, Cerulean Blue, Alkaline Blue Lu Lake, Peacock Blue Lake, Victoria Blue Lake, Metal-free Phthalocyanine Blue, Phthalocyanine Blue, Fast Sky Blue, Indanthrene Blue (RS, BC), Indigo, Ultramarine Blue, Prussian Blue, Anthraquinone Blue, Fast Violet B, Methyl Violet Lake, Cobalt Purple, Manganese Purple, Dioxane Violet, Anthraquinone Violet, Chrome Green, Zinc Green, Chromium Oxide, Pyridian, Emerald Green, Pigment Green B, Naphthol Green B, Green Gold, Acid Green Lake,Malachite green lake, phthalocyanine green, anthraquinone green, titanium oxide, zinc oxide, lithopone, and mixtures thereof.

[0096] The content of the colorant in the toner is usually 1% by mass to 15% by mass, and preferably 3% by mass to 10% by mass.

[0097] The colorant may also be used as a master batch in which it is combined with a resin. Examples of resins used in the preparation of the masterbatch or kneaded with the masterbatch include polymers of styrene and its substitutes, such as polystyrene, poly-p-chlorostyrene, and polyvinyl toluene, or copolymers of these with vinyl compounds, polymethyl methacrylate, polybutyl methacrylate, polyvinyl chloride, polyvinyl acetate, polyethylene, polypropylene, polyester resins, epoxy resins, epoxy polyol resins, polyurethane resins, polyamide resins, polyvinyl butyral resins, polyacrylic acid resins, rosin, modified rosin, terpene resins, aliphatic or alicyclic hydrocarbon resins, and aromatic petroleum resins, and these can be used alone or in combination.

[0098] The master batch can be obtained by mixing and kneading the resin and the colorant for the master batch with high shear force. In this case, an organic solvent can be used to enhance the interaction between the colorant and the resin. In addition, a method called a flushing method in which an aqueous paste containing water of the colorant is mixed and kneaded with the resin and the organic solvent, the colorant is transferred to the resin side, and the water and the organic solvent component are removed is also preferably used because the wet cake of the colorant can be used as it is and there is no need to dry it. For the mixing and kneading, a high shear dispersing device such as a three-roll mill is preferably used.

[0099] --Charge control agent-- The charge control agent may be any of those known in the art, and examples of such agents include nigrosine dyes, triphenylmethane dyes, chromium-containing metal complex dyes, molybdic acid chelate pigments, rhodamine dyes, alkoxy amines, quaternary ammonium salts (including fluorine-modified quaternary ammonium salts), alkylamides, phosphorus simple substance or compounds, tungsten simple substance or compounds, fluorine-based activators, metal salicylic acid salts, and metal salts of salicylic acid derivatives.

[0100] Specifically, the charge control agent includes Nigrosine dye Bontron 03, quaternary ammonium salt Bontron P-51, metal-containing azo dye Bontron S-34, oxynaphthoic acid metal complex E-82, salicylic acid metal complex E-84, phenol condensate E-89 (all manufactured by Orient Chemical Industry Co., Ltd.), quaternary ammonium salt molybdenum complex TP-302 and TP-415 (all manufactured by Hodogaya Chemical Co., Ltd.), quaternary ammonium salt Copy Charge PSY VP2038, triphenylmethane derivative Copy Blue PR, quaternary ammonium salt Copy Charge NEG VP2036, and Copy Charge NX. Examples of the pigments include VP434 (manufactured by Hoechst), LRA-901, boron complex LR-147 (manufactured by Nippon Carlit Co., Ltd.), copper phthalocyanine, perylene, quinacridone, azo pigments, and polymeric compounds having functional groups such as sulfonic acid groups, carboxyl groups, and quaternary ammonium salts. These pigments may be used alone or in combination of two or more. Among these, substances that control the toner to be negatively polarized are particularly preferred.

[0101] The amount of the charge control agent used is determined by the type of the binder resin, the presence or absence of additives used as necessary, the toner manufacturing method including the dispersion method, and the like, and is not uniquely limited. However, the charge control agent is preferably used in the range of 0.1 parts by mass to 10 parts by mass, and more preferably used in the range of 0.2 parts by mass to 5 parts by mass, relative to 100 parts by mass of the binder resin.

[0102] --External additives-- As the external additive, any known additive can be used, but inorganic fine particles are preferably used as an external additive for improving the fluidity, developability, and chargeability of the toner particles.

[0103] The primary particle size of the inorganic fine particles is not particularly limited, but is preferably 5×10 -3 μm to 2 μm, and preferably 5×10 -3 It is particularly preferable that the thickness is 0.5 μm to 0.5 μm.

[0104] The specific surface area of ​​the inorganic fine particles according to the BET method is not particularly limited, but is preferably 20 m 2 / g~500m 2 It is preferable that the molecular weight is 1 / g.

[0105] The content of the inorganic fine particles is not particularly limited, but is preferably 0.01% by mass to 5% by mass, and particularly preferably 0.01% by mass to 2.0% by mass, based on the toner.

[0106] Specific examples of the inorganic fine particles include silica, alumina, titanium oxide, barium titanate, magnesium titanate, calcium titanate, strontium titanate, zinc oxide, tin oxide, silica sand, clay, mica, wollastonite, diatomaceous earth, chromium oxide, cerium oxide, red iron oxide, antimony trioxide, magnesium oxide, zirconium oxide, barium sulfate, barium carbonate, calcium carbonate, silicon carbide, and silicon nitride. Examples of the inorganic fine particles include polymeric fine particles such as polystyrene obtained by soap-free emulsion polymerization, suspension polymerization, or dispersion polymerization; copolymers of methacrylic acid esters and acrylic acid esters; polycondensation systems such as silicone, benzoguanamine, and nylon; and polymer particles made of thermosetting resins. These may be used alone or in combination of two or more.

[0107] The external additive is preferably one that has been surface-treated to improve its hydrophobicity, in order to prevent deterioration of flow characteristics and charging characteristics even under high humidity conditions.

[0108] Examples of the surface treatment agent used in the external additive include a silane coupling agent (e.g., a silane coupling agent having a fluoroalkyl group), a silylation agent, an organic titanate coupling agent, an aluminum coupling agent, silicone oil, and modified silicone oil.

[0109] Among these, it is preferable to use, as the external additive, hydrophobic silica or hydrophobic titanium oxide obtained by subjecting silica or titanium oxide to the above-mentioned surface treatment.

[0110] -Toner Tg- The Tg of the toner is not particularly limited, but is preferably from 35° C. to 60° C., and more preferably from 45° C. to 55° C. in terms of heat-resistant storage stability. The Tg of the toner can be obtained by the DSC apparatus described in the section "-Wax-." Specifically, the Tg of the toner can be obtained from a DSC curve obtained by heating the toner sample from room temperature to 150° C. and then measuring the second heating from room temperature.

[0111] -Average thickness of shell layer- The average thickness of the shell layer in the toner is not particularly limited, but is preferably 200 nm to 400 nm. The average thickness of the shell layer can be measured using a transmission electron microscope (TEM). Specifically, the toner is embedded in an epoxy resin and cured, then cut with a knife, and an ultrathin section of the toner having a thickness of 80 nm is prepared using an ultramicrotome ULTRACUT UCT (manufactured by Leica). Next, the ultrathin section is exposed to ruthenium tetroxide gas for 5 minutes to distinguish and stain the shell and the core. Furthermore, the ultrathin section of the toner is observed at an acceleration voltage of 100 kV using a TEM (transmission electron microscope) H7000 (manufactured by Hitachi High-Tech Corporation) to measure the shell thickness. At this time, the shell thickness of 10 randomly measured toner particles is measured, and the average value is calculated.

[0112] -Volume average particle size of toner (Dv)- The volume average particle diameter (Dv) of the toner is not particularly limited, but is preferably from 3.0 μm to 8.0 μm, and more preferably from 3.0 μm to 6.0 μm. It is also preferable that the ratio of toner particles having a volume average particle size (Dv) of 3 μm or less is 10% by volume or less with respect to all toner particles.

[0113] -Toner particle size distribution (Dv / Dn)- The ratio (Dv / Dn) of the volume average particle diameter (Dv) to the number average particle diameter (Dn) of the toner as the particle size distribution of the toner is not particularly limited, but is preferably 1.00 to 1.40, and more preferably 1.00 to 1.15, in terms of excellent heat resistance storage stability, low temperature fixing property, and hot offset resistance, and in particular, excellent image gloss when used in a full-color copier or the like.

[0114] The volume average particle diameter (Dv), number average particle diameter (Dn), and particle size distribution (Dv / Dn) of the toner can be measured by various methods, for example, using a precision particle size distribution measuring device (Multisizer 3, manufactured by Beckman Coulter, Inc.).

[0115] -Circularity of toner- The average circularity of the toner is not particularly limited, but is preferably in the range of 0.93 to 1.00, and more preferably 0.94 to 0.97. The circularity of the toner is a value obtained by optically detecting a particle and dividing the particle by the perimeter of a circle having the same projected area. Specifically, it can be measured using a flow-type particle image analyzer (FPIA-3000, manufactured by Toa Medical Electronics Co., Ltd.). In a specific measurement method, 0.1 mL to 0.5 mL of a surfactant, preferably an alkylbenzene sulfonate, is added as a dispersant to 100 mL to 150 mL of water from which solid impurities have been removed in advance in a container, and about 0.1 g to 0.5 g of a toner sample is further added as a measurement sample. The suspension in which the toner sample is dispersed is subjected to a dispersion treatment for about 1 minute to about 3 minutes with an ultrasonic disperser, and the shape and distribution of the toner are measured with the flow type particle image analyzer at a dispersion concentration of 3,000 particles / μL to 10,000 particles / μL.

[0116] The toner has a substantially spherical shape, which can be expressed by the following shape definition. 1A to 1C are diagrams each showing an example of the shape of the toner. In FIG. 1A to FIG. 1C, when a toner having a substantially spherical shape is represented by three-dimensional axes of x-axis, y-axis, and z-axis, the major axis r 1 , short axis r 2 , and thickness r 3 (However, 1 ≧r 2 ≧r 3 ), the toner has a thickness r 3 and the major axis r 1 Ratio to (r 3 / r 1 ) is in the range of 0.5 to 1.0 (see Figure 1B), and the thickness r 3 and minor axis r 2 Ratio to (r 3 / r 2 ) is preferably in the range of 0.7 to 1.0 (see FIG. 1C). 3 and minor axis r 2 Ratio to (r 3 / r 2 ) is 1.0, the major axis r 1 This is preferable in that it becomes a rotating body with the axis of rotation and can improve the fluidity of the toner. In addition, the major axis r 1 , short axis r 2 , and thickness r 3 can be measured by taking photographs at different viewing angles using a scanning electron microscope (SEM).

[0117] The toner can be used as a one-component magnetic toner that does not use a magnetic carrier, or as a non-magnetic toner. When the toner is used in a two-component developer, it may be mixed with a magnetic carrier.

[0118] The magnetic carrier is not particularly limited, but is preferably a ferrite containing a divalent metal such as iron, magnetite, manganese (Mn), zinc (Zn), or copper (Cu) and has a volume average particle size of 20 μm to 100 μm. Cu ferrite containing Zn is preferred because it has high saturation magnetization, but can be appropriately selected according to the process of the image forming device.

[0119] The resin that coats the magnetic carrier is not particularly limited, and examples thereof include silicone resin, styrene-acrylic resin, fluorine-containing resin, and olefin resin.

[0120] The method for producing the magnetic carrier may involve dissolving the resin coated with the resin (coating resin) in a solvent and spraying it into a fluidized bed to coat the cores, or may involve electrostatically attaching resin particles to core particles and then heat-melting the particles to coat them.

[0121] The thickness of the resin coating is not particularly limited, but is preferably 0.05 μm to 10 μm, and more preferably 0.3 μm to 4 μm.

[0122] --Toner manufacturing method-- The toner production method will be described below. Here, a so-called solution suspension method will be described as a preferred embodiment of the method for producing the toner core particles, but the method is not limited to this, and the toner core particles may be produced by a pulverization method, an (emulsion) aggregation method, or other methods. The toner production is preferably carried out according to the following 1) to 4), and more preferably further includes the following 5).

[0123] 1) The polyester prepolymer (A) having an isocyanate group, the wax, preferably the unmodified polyester (i), and, if necessary, the colorant are dispersed in an organic solvent to prepare a toner material liquid (core material liquid).

[0124] The organic solvent is not particularly limited, but a volatile organic solvent having a boiling point of less than 100° C. is preferred because it is easy to remove after the formation of the toner base particles. Specific examples of the organic solvent include toluene, xylene, benzene, carbon tetrachloride, methylene chloride, 1,2-dichloroethane, 1,1,2-trichloroethane, trichloroethylene, chloroform, monochlorobenzene, dichloroethylidene, methyl acetate, ethyl acetate, methyl ethyl ketone, and methyl isobutyl ketone, which can be used alone or in combination of two or more. Among these, the organic solvent is particularly preferably an aromatic solvent such as toluene or xylene, and a halogenated hydrocarbon such as methylene chloride, 1,2-dichloroethane, chloroform, or carbon tetrachloride.

[0125] The amount of the organic solvent used is usually 0 to 300 parts by mass, preferably 0 to 100 parts by mass, and more preferably 25 to 70 parts by mass, based on 100 parts by mass of the polyester prepolymer (A) having an isocyanate group.

[0126] 2) The toner material liquid obtained in 1) is emulsified in an aqueous medium. In order to improve the dispersibility of the toner material in the aqueous medium, a dispersant such as a surfactant, resin particles, or an inorganic compound may be appropriately added.

[0127] The aqueous medium may be water alone, or may contain an organic solvent such as alcohol (e.g., methanol, isopropyl alcohol, ethylene glycol), dimethylformamide, tetrahydrofuran, cellosolves (e.g., methyl cellosolve), or lower ketones (e.g., acetone, methyl ethyl ketone).

[0128] The amount of the aqueous medium used is usually 50 parts by mass to 2,000 parts by mass, and preferably 100 parts by mass to 1,000 parts by mass, based on 100 parts by mass of the toner material liquid.

[0129] The Tg of the resin fine particles dispersed in the aqueous medium is preferably 50°C to 110°C, more preferably 50°C to 90°C, and further preferably 50°C to 70°C. The weight average molecular weight of the resin fine particles is preferably 100,000 or less, more preferably 50,000 or less, and the lower limit thereof is usually 4,000.

[0130] The surfactant is not particularly limited, and examples thereof include anionic surfactants such as alkylbenzenesulfonates, α-olefinsulfonates, and phosphoric acid esters; cationic surfactants of amine salt type such as alkylamine salts, aminoalcohol fatty acid derivatives, polyamine fatty acid derivatives, and imidazolines; cationic surfactants of quaternary ammonium salt type such as alkyltrimethylammonium salts, dialkyldimethylammonium salts, alkyldimethylbenzylammonium salts, pyridinium salts, alkylisoquinolinium salts, and benzethonium chloride; nonionic surfactants such as fatty acid amide derivatives and polyhydric alcohol derivatives; and amphoteric surfactants such as alanine, dodecyldi(aminoethyl)glycine, di(octylaminoethyl)glycine, and N-alkyl-N,N-dimethylammonium betaine. These may be used alone or in combination of two or more.

[0131] Furthermore, by using a surfactant having a fluoroalkyl group, the effect can be achieved with a very small amount. Examples of anionic surfactants having a fluoroalkyl group that are preferably used include fluoroalkyl carboxylic acids having 2 to 10 carbon atoms and metal salts thereof, disodium perfluorooctanesulfonyl glutamate, sodium 3-[ω-fluoroalkyl(C6 to C11)oxy]-1-alkyl(C3 to C4)sulfonate, sodium 3-[ω-fluoroalkanoyl(C6 to C8)-N-ethylamino]-1-propanesulfonate, fluoroalkyl(C11 to C20)carboxylic acids and metal salts, perfluoroalkyl Examples of such compounds include carboxylic acids (C7-C13) and their metal salts, perfluoroalkyl (C4-C12) sulfonic acids and their metal salts, perfluorooctanesulfonic acid diethanolamide, N-propyl-N-(2-hydroxyethyl)perfluorooctanesulfonamide, perfluoroalkyl (C6-C10) sulfonamidopropyl trimethylammonium salts, perfluoroalkyl (C6-C10)-N-ethylsulfonylglycine salts, and monoperfluoroalkyl (C6-C16) ethyl phosphate esters. Here, the "C" indicates the number of carbon atoms.

[0132] Examples of commercially available anionic surfactants having a fluoroalkyl group include, by trade name, Surflon S-111, Surflon S-112, Surflon S-113 (all manufactured by AGC Seimi Chemical Co., Ltd.), Fluorad FC-93, Fluorad FC-95, Fluorad FC-98, Fluorad FC-129 (all manufactured by Sumitomo 3M Limited), Unidyne DS-101, Unidyne DS-102 (all manufactured by Daikin Industries, Ltd.), Megafac F-110, Megafac F-120, Megafac F-113, Megafac F-191, Megafac F-812, Megafac F-833 (all manufactured by DIC Corporation), F-top EF-102, F-top EF-103, F-top EF-104, F-top EF-105, F-top EF-112, F-top EF-123A, F-top EF-123B, F-top EF-306A, F-top EF-501, F-top EF-201, F-top EF-204 (all manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.), Ftergent 100, Ftergent 150 (manufactured by Neos Corporation), etc.

[0133] Examples of cationic surfactants having a fluoroalkyl group include aliphatic primary or secondary amine acids having a fluoroalkyl group, aliphatic quaternary ammonium salts such as perfluoroalkyl (C6 to C10) sulfonamidopropyltrimethylammonium salts, benzalkonium salts, benzethonium chloride, pyridinium salts, and imidazolinium salts.

[0134] Examples of commercially available cationic surfactants having a fluoroalkyl group include, by product name or trade name, Surflon S-121 (manufactured by AGC Seimi Chemical Co., Ltd.), Fluorad FC-135 (manufactured by Sumitomo 3M Limited), Unidyne DS-202 (manufactured by Daikin Industries, Ltd.), Megafac F-150, Megafac F-824 (all manufactured by DIC Corporation), F-top EF-132 (manufactured by Mitsubishi Materials Electronic Chemicals Co., Ltd.), and Ftergent 300 (manufactured by NEOS Corporation).

[0135] The resin fine particles may be any known resin fine particles that can form the aqueous dispersion, and may be a thermoplastic resin or a thermosetting resin. Examples of the resin fine particles include vinyl resins, polyurethane resins, epoxy resins, and polyester resins. These may be used alone or in combination of two or more. Among these, the resin fine particles are preferably vinyl resins, polyurethane resins, epoxy resins, polyester resins, polystyrene resins, or combinations thereof, because they are easy to obtain an aqueous dispersion of fine spherical resin particles.

[0136] The vinyl resin is a polymer obtained by homopolymerizing or copolymerizing a vinyl monomer, and examples thereof include styrene-acrylic acid ester resin, styrene-methacrylic acid ester resin, styrene-butadiene copolymer, acrylic acid-acrylic acid ester polymer, methacrylic acid-acrylic acid ester polymer, styrene-acrylonitrile copolymer, styrene-maleic anhydride copolymer, styrene-acrylic acid copolymer, and styrene-methacrylic acid copolymer.

[0137] Specific examples of the resin fine particles include polymethyl methacrylate fine particles, polystyrene fine particles, and poly(styrene-acrylonitrile) fine particles.

[0138] Commercially available resin microparticles include, for example, trade names such as PB-200H (manufactured by Kao Corporation), SGP-3G (both manufactured by Soken Chemical & Engineering Co., Ltd.), Technopolymer SB (manufactured by Sekisui Chemical Industry Co., Ltd.), and Micropearl (manufactured by Sekisui Fine Chemical Co., Ltd.).

[0139] The resin particles are added to stabilize the toner base particles formed in the aqueous medium or to prevent the wax from being exposed to the outermost surface of the toner. For this reason, the resin particles are preferably added so that the coverage of the resin particles on the surface of the toner base particles is in the range of 10% to 90%.

[0140] The volume average particle diameter of the resin fine particles is preferably 200 nm to 300 nm, as measured by a light scattering photometer (manufactured by Otsuka Electronics Co., Ltd.).

[0141] The inorganic compound is not particularly limited, and examples thereof include tricalcium phosphate, calcium carbonate, titanium oxide, colloidal silica, and hydroxyapatite.

[0142] The dispersion method is not particularly limited, but known equipment such as low-speed shear type, high-speed shear type, friction type, high-pressure jet type, and ultrasonic type can be applied. Among these, the high-speed shear type is preferred in order to make the particle size of the dispersion 2 μm to 20 μm. When using a high-speed shear type dispersing machine, the rotation speed is not particularly limited, but is usually 1,000 rpm to 30,000 rpm, preferably 5,000 rpm to 20,000 rpm. The dispersion time is not particularly limited, but is usually 0.1 minutes to 5 minutes in the case of a batch method. The temperature during dispersion is usually 0°C to 150°C (under pressure), preferably 40°C to 98°C.

[0143] 3) At the same time as preparing the emulsion, the amines (B) are added and reacted with the polyester prepolymer (A) having an isocyanate group. This reaction involves crosslinking and / or elongation of molecular chains. There is no particular limit to the reaction time, which is selected depending on the reactivity between the isocyanate group structure of the polyester prepolymer (A) and the amines (B), and is usually 10 minutes to 40 hours, preferably 2 hours to 24 hours. There is no particular limit to the reaction temperature, which is usually 0°C to 150°C, preferably 40°C to 98°C. If necessary, a known catalyst can be used. Specific examples of the catalyst include dibutyltin laurate and dioctyltin laurate.

[0144] 4) After the reaction of 3) is completed, the organic solvent is removed from the resulting emulsion dispersion (reaction product), which is then washed and dried to obtain toner base particles. In order to remove the organic solvent, the temperature of the entire system is gradually raised in a state of laminar agitation, and after strong agitation is applied in a certain temperature range, the solvent is removed to produce spindle-shaped toner base particles. When a substance that can be dissolved in acid or alkali, such as calcium phosphate, is used as the dispersant, the calcium phosphate is dissolved with an acid such as hydrochloric acid, and then the calcium phosphate is removed from the toner base particles by a method such as washing with water. Alternatively, the calcium phosphate can be removed by a procedure such as decomposition with an enzyme.

[0145] 5) If necessary, the charge control agent is implanted into the toner base particles obtained in 4), and then inorganic fine particles such as silica fine particles and titanium oxide fine particles are added as the external additive to obtain a toner. The injection of the charge control agent and the external addition of the inorganic fine particles are carried out by a known method using a mixer or the like. This makes it possible to easily obtain a toner having a small particle size and a sharp particle size distribution. Furthermore, by applying strong stirring in the process of removing the organic solvent, the shape of the toner can be controlled to be anywhere between a perfect sphere and a rugby ball shape, and the surface morphology can also be controlled to be anywhere between a smooth shape and a pickled plum shape.

[0146] <<Recording Media>> The recording medium is not particularly limited, and examples thereof include paper, cloth, and sheets for an overhead projector (OHP).

[0147] (Image forming apparatus and image forming method) The image forming apparatus of the present invention comprises an electrostatic latent image carrier (sometimes referred to as a "photoconductor"), an electrostatic latent image forming means for forming an electrostatic latent image on the electrostatic latent image carrier, a developing means for developing the electrostatic latent image with a developer containing a toner to form a visible image (toner image), a transfer means for transferring the visible image carried on the electrostatic latent image carrier onto a recording medium, and a fixing device for fixing the transferred image transferred onto the recording medium, wherein the toner is a toner used in the image fixing method of the present invention, and the fixing device is an image fixing device used in the image fixing method of the present invention. The electrostatic latent image forming means preferably includes at least a charging means (charger) for uniformly charging the surface of the photoreceptor, and an exposure means (exposure device) for imagewise exposing the surface of the electrostatic latent image carrier.

[0148] In addition, the image forming apparatus may further include, as necessary, a cleaning means for removing the toner remaining on the photosensitive member, a discharging means for applying a discharging bias to the photosensitive member to remove electricity, and a recycling means for recycling the toner removed by the cleaning means to the developing means.

[0149] The image forming method of the present invention includes an electrostatic latent image forming step of forming an electrostatic latent image on an electrostatic latent image carrier, a developing step of developing the electrostatic latent image with a developer containing a toner to form a visible image, a transfer step of transferring the visible image onto a recording medium, and a fixing step of fixing the transferred image transferred onto the recording medium by an image fixing device, wherein the toner is a toner used in the image fixing method of the present invention, and the fixing step is performed by the image fixing method of the present invention.

[0150] The image forming method may further include, as necessary, a cleaning step of removing the toner remaining on the photoreceptor, a discharging step of applying a discharging bias to the photoreceptor to remove electricity therefrom, and a recycling step of recycling the toner removed in the cleaning step.

[0151] The electrostatic latent image forming process can be suitably performed by an electrostatic latent image forming means, the developing process can be suitably performed by the developing means, the transfer process can be suitably performed by the transfer means, the cleaning process can be suitably performed by the cleaning means, the discharging process can be suitably performed by the discharging means, and the recycling process can be suitably performed by the recycling means.

[0152] As a specific example, the photoconductor is rotated at a predetermined peripheral speed. During the rotation process, the photoconductor is uniformly charged to a predetermined positive or negative potential on its peripheral surface by the charging means, and then receives image exposure light from the exposure means such as slit exposure or laser beam scanning exposure, thus forming electrostatic latent images on the peripheral surface of the photoconductor. The electrostatic latent images thus formed are then developed with toner by the developing means, and the developed toner images are sequentially transferred by the transfer means to a recording medium (including an intermediate transfer member) fed from a recording medium supply unit between the photoconductor and the transfer means in synchronization with the rotation of the photoconductor. The recording medium to which the image has been transferred is separated from the photoconductor surface and introduced into the fixing means where the image is fixed, and is printed out as a duplicate (copy) outside the device. The surface of the photoconductor after the image transfer is cleaned by removing the remaining toner by the cleaning means, and is further discharged, and is then returned to the developing means by the recycling means for repeated use in image formation.

[0153] The image forming apparatus preferably applies an alternating electric field when developing a latent image on a photoconductor.

[0154] FIG. 3 shows an example of the developing means in the image forming apparatus of the present invention. In the developing device 20 shown in Fig. 3, during development, an oscillating bias voltage, which is a DC voltage superimposed with an AC voltage, is applied to the developing sleeve 21 by the power source 22 as a developing bias. The background portion potential and the image portion potential are located between the maximum and minimum values ​​of the oscillating bias potential. This forms an alternating electric field in the developing section 23, the direction of which alternates. In this alternating electric field, the toner and carrier of the developer vibrate violently, and the toner breaks free from the electrostatic binding force on the developing sleeve 21 and the carrier, flies to the photoconductor drum 24, and adheres to the latent image on the photoconductor drum 24.

[0155] The difference between the maximum and minimum values ​​of the oscillating bias voltage (peak-to-peak voltage) is preferably 0.5 KV to 5 KV, and the frequency is preferably 1 KHz to 10 KHz. The waveform of the oscillating bias voltage may be a square wave, a sine wave, a triangular wave, or the like. As described above, the DC voltage component of the oscillating bias has a value between the background portion potential and the image portion potential, but a value closer to the background portion potential than the image portion potential is preferable in terms of preventing adhesion of fog toner to the background portion potential area.

[0156] When the waveform of the oscillating bias voltage is a square wave, it is desirable to set the duty ratio to 50% or less. Here, the duty ratio is the ratio of the time during which the toner moves toward the photoconductor during one cycle of the oscillating bias. By doing so, the difference between the peak value at which the toner moves toward the photoconductor and the time average value of the bias can be increased, so that the movement of the toner becomes more active, and the toner adheres faithfully to the potential distribution of the latent image surface, improving the roughness and resolution. In addition, the difference between the peak value at which the carrier, which has a charge of the opposite polarity to the toner, moves toward the photoconductor and the time average value of the bias can be reduced, so that the movement of the carrier can be calmed down, and the probability of the carrier adhering to the background part of the latent image can be greatly reduced.

[0157] It is preferable that the charging device of the image forming apparatus performs charging by bringing a charging member into contact with the electrostatic latent image bearing member and applying a voltage to the charging member.

[0158] The charging member may have any shape, which can be selected according to the specifications and shape of the image forming apparatus. Examples of the charging member include a roller, a fur brush, and a magnetic brush.

[0159] <In the case of roller charging> 5A shows a schematic configuration of an example of an image forming apparatus using a contact-type charging device. A photoconductor 31, which is an image carrier and is a body to be charged, is rotated in the direction of the arrow at a predetermined speed (process speed). A charging roller 32, which is a charging member in contact with the photoconductor 31, is basically composed of a core metal 33 and a conductive rubber layer 34 formed on the roller concentrically integral with the outer periphery of the core metal 33. Both ends of the core metal 33 are held rotatably by a bearing member (not shown) and pressed against the photoconductor 31 with a predetermined pressure by a pressure means (not shown). In this figure, the charging roller 32 rotates following the rotation of the photoconductor 31.

[0160] When a charging roller is used, it is common to coat a layer of rubber with a medium resistance of about 100,000 Ω·cm on a core metal, and for example, charging roller 32 may be formed to a diameter of 16 mm by coating a layer of rubber with a medium resistance of about 100,000 Ω·cm on a core metal 33 with a diameter of 9 mm. The core metal 33 of charging roller 32 is electrically connected to a power source 35, and a predetermined bias is applied to charging roller 32 by power source 35. As a result, the peripheral surface of photoconductor 31 is uniformly charged to a predetermined polarity and potential. Figure 4 is a diagram showing the charging characteristics of contact charging.

[0161] <In the case of fur brush charging or magnetic brush charging> 5B shows a schematic configuration of an example of an image forming apparatus using a contact-type charging device. Photoconductor 41, which serves as a charged body and image carrier, is rotated in the direction of the arrow at a predetermined speed (process speed). Brush roller 42, which is composed of brush section 44 made of a fur brush or magnetic brush and core metal 43, is in contact with photoconductor 41 with a predetermined nip width and with a predetermined pressing force against the elasticity of brush section 44.

[0162] <<Fur brush>> The material of the fur brush may be, for example, fur that has been treated to be conductive with carbon, copper sulfide, metal, or metal oxide, and this can be made into a charging member by wrapping or attaching it to a metal or other conductive core.

[0163] The fur brush preferably has a density of 80 fibers / mm to 600 fibers / mm, with each fiber having a denier of 3 to 10 denier, and with a filament density of 10 to 100 filaments / bundle.

[0164] A specific example of the fur brush is a roll brush having an outer diameter of 14 mm and a longitudinal length of 250 mm, which is made by spirally winding a tape of conductive rayon fiber (e.g., REC-B, manufactured by Unitika Ltd.) pile fabric as a brush part around a metal core having a diameter of 6 mm, which also serves as an electrode. The brush of the brush part 44 is preferably 300 denier / 50 filament, with a density of 155 fibers per square millimeter. This roll brush is preferably inserted into a pipe having an inner diameter of 12 mm while rotating in one direction, so that the brush and the pipe are set concentrically, and left in a high-temperature, high-humidity atmosphere to form a slanted hair pattern.

[0165] Materials that can be used for the front fur brush include other than the above-mentioned REC-B (manufactured by Unitika Ltd.), such as REC-C, REC-M1, REC-M10 (all manufactured by Unitika Ltd.), SA-7 (manufactured by Toray Industries, Inc.), Thunderon (manufactured by Nippon Sanmo Dyeing Co., Ltd.), Belltron (manufactured by Kanebo Cosmetics Inc.), Clacarbo (manufactured by Kuraray Co., Ltd.), and Robal (manufactured by Mitsubishi Rayon Co., Ltd.). Rayon with carbon dispersed therein can also be used.

[0166] The resistance value of the fur brush roller is not particularly limited, but is preferably 1×10 5 This resistance value is calculated from the current that flows when a voltage of 100 V is applied to a metal drum having a diameter of φ30 mm and a fur brush roller with a nip width of 3 mm.

[0167] The resistance value of the fur brush charger is 100%, in that even if a low-voltage defective portion such as a pinhole occurs on the photoconductor to be charged, an excessive leakage current flows into this portion, preventing image defects caused by insufficient charging of the charging nip portion. 4 Ω or more is preferable, and 10 7 Ω or less is preferable.

[0168] The brush roller 42 is driven to rotate at a predetermined peripheral speed (surface speed) in the opposite direction (counter) to the rotational direction of the photoconductor 41, and contacts the surface of the photoconductor 41 with a speed difference. A predetermined charging voltage is applied to the brush roller 42 from a power source 45, so that the rotating photoconductor surface is uniformly contact-charged to a predetermined polarity and potential. In this example, the contact charging of the photoconductor 41 by the fur brush roller 42 is performed predominantly by direct injection charging, and the surface of the rotating photoconductor 41 is charged to a potential substantially equal to the charging voltage applied to the brush roller 42.

[0169] <<Magnetic brush>> The magnetic brush preferably uses various ferrite particles, such as Zn-Cu ferrite, as a charging member, and is composed of a non-magnetic conductive sleeve for supporting the magnetic brush, and a magnet roll contained therein.

[0170] A specific example of the magnetic brush is a configuration in which Zn-Cu ferrite particles with an average particle size of 25 μm and Zn-Cu ferrite particles with an average particle size of 10 μm are mixed in a weight ratio of 1:0.05, and the ferrite particles with an average particle size of 25 μm, which have a peak at the position of each average particle size, are coated with a medium resistance resin layer to form magnetic particles (coated magnetic particles) on the non-magnetic conductive sleeve to a thickness of 1 mm, forming a charging nip with a width of approximately 5 mm between the photosensitive body and the magnetic particle retaining sleeve, the gap between the magnetic particle retaining sleeve and the photosensitive body being approximately 500 μm, and further, the magnet roll is rotated so that the sleeve surface rubs in the opposite direction at twice the peripheral speed of the photosensitive body surface, so that the photosensitive body and the magnetic brush are in uniform contact with each other. EXAMPLES

[0171] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the following examples, "parts" refers to "parts by mass".

[0172] The magnetic carrier used in the two-component developer was the same in each of the examples as follows. (Magnetic carrier manufacturing) Core material: Cu-Zn ferrite particles (weight average particle size: 35 μm) 5,000 parts Coating materials Toluene 450 parts Silicone resin SR2400 (Made by Toray Dow Corning Silicone, non-volatile content 50%) 450 parts Aminosilane SH6020 (Made by Toray Dow Corning Silicone) 10 parts Carbon black 10 parts

[0173] The coating material was dispersed with a stirrer for 10 minutes to prepare a coating liquid, and the coating liquid and the core material were put into a coating device that forms a swirling flow in a fluidized bed with a rotating bottom plate disk and stirring blades, and the coating liquid was applied onto the core material. The resulting coating was baked in an electric furnace at 250°C for 2 hours to obtain a magnetic carrier coated with the silicone resin to an average thickness of 0.5 μm.

[0174] (Preparation of two-component developer) A two-component developer was prepared by uniformly mixing and charging 7 parts by mass of the toner shown in the following Examples 1 to 9 and Comparative Examples 1 and 2 with 100 parts by mass of the magnetic carrier using a turbulator mixer that rotates the container to mix.

[0175] Example 1 <Preparation of vinyl resin dispersion 1> In a reaction vessel equipped with a stirring rod and a thermometer, 683 parts of ion-exchanged water, 11 parts of sodium salt of sulfate ester of ethylene oxide adduct of methacrylic acid (Eleminol RS-30, manufactured by Sanyo Chemical Industries, Ltd.), 10 parts of polylactic acid, 60 parts of styrene, 100 parts of methacrylic acid, 70 parts of butyl acrylate, and 1 part of ammonium persulfate were added and stirred at a rotation speed of 3,800 rpm for 30 minutes, then the temperature was raised to 75 ° C. and reacted for 4 hours, after which 30 parts of 1 mass% aqueous ammonium persulfate solution was added and aged at 75 ° C. for 6 hours to obtain [Vinyl resin dispersion 1] as an aqueous dispersion of vinyl resin. The volume average particle size of [Vinyl resin dispersion 1] was measured using a laser diffraction / scattering particle size distribution measuring device (LA-920, manufactured by Horiba, Ltd.), and it was 280 nm. In addition, a part of [Vinyl resin dispersion 1] was dried to isolate the vinyl resin contained in [Vinyl resin dispersion 1]. The vinyl resin had a Tg of 59° C. and a weight average molecular weight of 60,000.

[0176] <Preparation of aqueous phase> 990 parts of water, 83 parts of [vinyl resin dispersion 1], 37 parts of a 48.3 mass% aqueous solution of sodium dodecyldiphenyletherdisulfonate (Eleminol MON-7, manufactured by Sanyo Chemical Industries, Ltd.), and 90 parts of ethyl acetate were mixed and stirred to obtain a milky white liquid, which was designated as [aqueous phase 1].

[0177] <Synthesis of low molecular weight polyester> In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 724 parts of bisphenol A ethylene oxide 2 mole adduct and 276 parts of terephthalic acid were placed and polycondensed at normal pressure at 230°C for 7 hours, and then reacted for 5 hours under reduced pressure of 10mmHg to 15mmHg to obtain [Low molecular weight polyester 1]. [Low molecular weight polyester 1] had a number average molecular weight of 2,300, a weight average molecular weight of 6,700, a peak molecular weight of 3,800, a Tg of 43°C, and an acid value of 4mgKOH / g.

[0178] <Synthesis of intermediate polyester> In a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, 682 parts of bisphenol A ethylene oxide 2 mole adduct, 81 parts of bisphenol A propylene oxide 2 mole adduct, 283 parts of terephthalic acid, 22 parts of trimellitic anhydride, and 2 parts of dibutyltin oxide were placed and reacted at normal pressure at 230°C for 7 hours, and then further reacted at a reduced pressure of 10mmHg to 15mmHg for 5 hours to obtain [Intermediate polyester 1]. [Intermediate polyester 1] had a number average molecular weight of 2,200, a weight average molecular weight of 9,700, a peak molecular weight of 3,000, a Tg of 54°C, an acid value of 0.5mgKOH / g, and a hydroxyl value of 52mgKOH / g. Next, 410 parts of [Intermediate polyester 1], 89 parts of isophorone diisocyanate, and 500 parts of ethyl acetate were placed in a reaction vessel equipped with a cooling tube, a stirrer, and a nitrogen inlet tube, and reacted at 100° C. for 5 hours to obtain [Prepolymer 1]. The free isocyanate mass% of [Prepolymer 1] was 1.53 mass%.

[0179] <Synthesis of ketimines> In a reaction vessel equipped with a stirring bar and a thermometer, 170 parts of isophoronediamine and 75 parts of methyl ethyl ketone were placed and reacted at 50°C for 4.5 hours to obtain [Ketimine Compound 1]. The amine value of [Ketimine Compound 1] was 417 mgKOH / g.

[0180] <Masterbatch synthesis> 1,200 parts of water, 540 parts of carbon black (Printex 35, manufactured by Degussa) [DBP oil absorption = 42 ml / 100 mg, pH = 9.5], and 1,200 parts of polyester resin were added and mixed in an FM mixer (manufactured by Nippon Coke and Engineering Co., Ltd.). The resulting mixture was kneaded using two rolls at 130°C for 1 hour, then rolled and cooled, and pulverized in a pulverizer to obtain [Masterbatch 1].

[0181] <Preparation of oil phase> In a reaction vessel equipped with a stirring rod and a thermometer, 378 parts of [low molecular weight polyester 1], 100 parts of carnauba wax, and 947 parts of ethyl acetate were charged, and the temperature was raised to 80°C while stirring, and the mixture was maintained at 80°C for 5 hours, and then cooled to 30°C in 1 hour. Next, 500 parts of [master batch 1] and 500 parts of ethyl acetate were charged in the vessel, and mixed for 1 hour to obtain [raw material solution 1].

[0182] 1,324 parts of [Raw material solution 1] was transferred to a container, and carbon black and wax were dispersed using a bead mill (Ultraviscomill, manufactured by Imex Co., Ltd.) with a liquid feed rate of 1 kg / hour, a disk peripheral speed of 6 m / sec, 80% by volume of 0.5 mm zirconia beads, and 3 passes. Next, 1,324 parts of a 65% by mass ethyl acetate solution of [Low molecular weight polyester 1] was added, and the bead mill was passed twice under the above conditions to obtain [Pigment-wax dispersion 1]. The solid concentration of [Pigment-wax dispersion 1] was 50% by mass.

[0183] <Emulsification> 749 parts of [Pigment-wax dispersion 1], 115 parts of [Prepolymer 1], and 2.9 parts of [Ketimine compound 1] were placed in a container and mixed for 2 minutes at 5,000 rpm with a TK Homomixer (manufactured by Tokushu Kika Kogyo Co., Ltd.), after which 1,200 parts of [Aqueous phase 1] was added to the container and mixed for 25 minutes at 13,000 rpm with the TK Homomixer to obtain [Emulsified slurry 1].

[0184] <Solvent removal> [Emulsified slurry 1] was placed in a container equipped with a stirrer and a thermometer, and the solvent was removed at 30°C for 7 hours, and then aged at 45°C for 7 hours to obtain [Dispersed slurry 1].

[0185] <Cleaning> [Dispersion Slurry 1] 100 parts was filtered under reduced pressure, I: 100 parts of ion-exchanged water was added to the filter cake, mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. II: 100 parts of a 10% by mass aqueous sodium hydroxide solution was added to the filter cake of I, and the mixture was mixed with a TK homomixer (at a rotation speed of 12,000 rpm for 10 minutes), and then filtered under reduced pressure. III: 100 parts of 10% by mass hydrochloric acid was added to the filter cake of II, and the mixture was mixed with a TK homomixer (at 12,000 rpm for 10 minutes), and then filtered. IV: 300 parts of ion-exchanged water was added to the filter cake of III, and the mixture was mixed with a TK homomixer (at 12,000 rpm for 10 minutes), followed by filtering twice to obtain [filter cake 1].

[0186] <Drying> [Filter cake 1] was dried in a circulating air dryer at 45°C for 48 hours and sieved through a 75μm mesh to obtain [toner base particle 1]. Then, 100 parts of [toner base particle 1] was mixed with 1 part of hydrophobic silica and 1 part of hydrophobic titanium oxide in an FM mixer to obtain [toner 1]. The physical properties of the obtained [toner 1] are shown in Table 1, and the evaluation results are shown in Table 2.

[0187] Example 2 [Toner 2] was obtained in the same manner as in Example 1, except that the <Preparation of Oil Phase> step in Example 1 was changed to the following conditions. The physical properties of the obtained [Toner 2] are shown in Table 1, and the evaluation results are shown in Table 2.

[0188] <Preparation of oil phase> In a reaction vessel equipped with a stirring rod and a thermometer, 378 parts of [low molecular weight polyester 1], 100 parts of carnauba wax and rice wax (carnauba wax:rice wax = 7:3 (mass ratio)), and 947 parts of ethyl acetate were charged, and the temperature was raised to 80°C while stirring, and after maintaining at 80°C for 4 hours, it was cooled to 30°C in 1 hour. Next, 500 parts of [master batch 1] and 500 parts of ethyl acetate were charged in the vessel and mixed for 1 hour to obtain [raw material solution 2].

[0189] Transfer 1,324 parts of [Raw material dissolution liquid 2] to a container, and using a bead mill (Ultraviscomill, manufactured by Imex Co., Ltd.), with a liquid feeding rate of 1 kg / hour, a disk peripheral speed of 6 m / second, filled with 80% by volume of 0.5 mm zirconia beads, and under the conditions of 7 passes, disperse carbon black and wax. Then, add 1,324 parts of a 65% by mass ethyl acetate solution of [Low molecular weight polyester 1], and pass through the bead mill under the above conditions for 4 passes to obtain [Pigment - wax dispersion liquid 2]. The solid content concentration of [Pigment - wax dispersion liquid 2] was 50%.

[0190] (Example 3) In Example 1, [Toner 3] was obtained in the same manner as in Example 1, except that the process of <Preparation of oil phase> was changed to the following conditions. The physical properties of the obtained [Toner 3] are shown in Table 1, and the evaluation results are shown in Table 2.

[0191] <Preparation of oil phase> Charge 378 parts of [Low molecular weight polyester 1], 100 parts of ester wax (Nissan Electol (registered trademark) WEP - 4, melting point 71°C), and 947 parts of ethyl acetate into a reaction vessel equipped with a stirring rod and a thermometer. Heat the mixture to 80°C with stirring, hold it at 80°C for 5 hours, and then cool it to 30°C in 1 hour. Next, charge 500 parts of [Masterbatch 1] and 500 parts of ethyl acetate into the container and mix for 1 hour to obtain [Raw material dissolution liquid 3].

[0192] Transfer 1,324 parts of [Raw material dissolution liquid 3] to a container, and using a bead mill (Ultraviscomill, manufactured by Imex Co., Ltd.), with a liquid feeding rate of 1 kg / hour, a disk peripheral speed of 6 m / second, filled with 80% by volume of 0.5 mm zirconia beads, and under the conditions of 3 passes, disperse carbon black and wax. Then, add 1,324 parts of a 65% by volume ethyl acetate solution of [Low molecular weight polyester 1], and pass through the bead mill under the above conditions for 2 passes to obtain [Pigment - wax dispersion liquid 3]. The solid content concentration of [Pigment - wax dispersion liquid 3] was 50%.

[0193] (Comparative Example 1) <Method for producing a polymer> A flask equipped with a stirrer, a condenser, a thermometer, and a nitrogen inlet tube was charged with 300 g of methanol, 100 g of toluene, 570 g of styrene, 30 g of 2-acrylamido-2-methylpropanesulfonic acid, and 12 g of lauroyl peroxide, and solution polymerization was carried out at 65°C for 10 hours under stirring and nitrogen introduction. The content was removed from the flask, dried under reduced pressure, and then pulverized with a jet mill to produce Polymer A having a weight average molecular weight of 3,000.

[0194] <Toner manufacturing> Styrene 183 parts 2-Ethylhexyl acrylate 17 parts A polymer 0.1 part CI Pigment Yellow 17 7 parts Paraffin wax (melting point 68.3°C: Taisei Kosan Co., Ltd.) 32 parts Polymerization initiator (V-601, Fujifilm Wako Pure Chemical Industries, Ltd.) 10 parts

[0195] The above formulation was heated to 65° C. and uniformly dissolved or dispersed to obtain a monomer composition. Separately, 0.3 g of a silane coupling agent (KBE-903, manufactured by Shin-Etsu Chemical Co., Ltd.) was uniformly dispersed in 1,200 ml of ion-exchanged water, and 6 g of colloidal silica (Aerosil #200: manufactured by Nippon Aerosil Co., Ltd.) was added and further uniformly dispersed. The pH of this dispersion was adjusted to 6 with hydrochloric acid to prepare a dispersion medium system. The above-mentioned monomer composition was added to this dispersion medium system, and the mixture was stirred at 6,500 rpm for 60 minutes at 70° C. under a nitrogen atmosphere using a TK homomixer to granulate the monomer composition. Thereafter, the mixture was polymerized at 75° C. for 8 hours while stirring with a paddle stirring blade. After the polymerization reaction was completed, the reaction product was cooled, 42 g of a 20% by mass aqueous solution of sodium hydroxide was added, and the mixture was subjected to an alkali treatment overnight to dissolve the dispersant, and the mixture was filtered, washed with water, and dried to obtain [Toner 4]. The physical properties of the obtained [Toner 4] are shown in Table 1, and the evaluation results are shown in Table 2.

[0196] Example 4 [Toner 5] was obtained in the same manner as in Example 1, except that in <Synthesis of Masterbatch>, 100 parts of a polyester resin (Tg, 37°C) having a tertiary amine group as an adsorption group as a pigment dispersant was added and mixed with an FM mixer, and the resulting mixture was kneaded with a two-roll mill. The physical properties of the obtained [Toner 5] are shown in Table 1, and the evaluation results are shown in Table 2.

[0197] Example 5 [Toner 6] was obtained in the same manner as in Example 1, except that 100 parts of a styrene-polyethylene polymer (Tg 72°C, number average molecular weight 7,100) was added as a wax dispersant during <Preparation of oil phase> in Example 1. The physical properties of the obtained [Toner 6] are shown in Table 1, and the evaluation results are shown in Table 2.

[0198] Comparative Example 2 [Toner 7] was obtained in the same manner as in Example 1, except that the <Preparation of Oil Phase> step in Example 1 was changed to the following conditions. The physical properties of the obtained [Toner 7] are shown in Table 1, and the evaluation results are shown in Table 2.

[0199] <Preparation of oil phase> In a reaction vessel equipped with a stirring rod and a thermometer, 378 parts of [low molecular weight polyester 1], 50 parts of carnauba wax, and 947 parts of ethyl acetate were charged, and the temperature was raised to 80°C while stirring, and the temperature was maintained at 80°C for 1 hour, and then cooled to 30°C in 1 hour. Next, 500 parts of [master batch 1] and 500 parts of ethyl acetate were charged in the vessel and mixed for 10 minutes to obtain [raw material solution 4].

[0200] 1,324 parts of [Raw material solution 4] was transferred to a container, and carbon black and wax were dispersed using a bead mill (Ultraviscomill, manufactured by Imex Co., Ltd.) with a liquid feed rate of 1 kg / hour, a disk peripheral speed of 6 m / sec, 80% by volume of 0.5 mm zirconia beads, and one pass. Next, 1,324 parts of a 65% by mass ethyl acetate solution of [Low molecular weight polyester 1] was added, and one pass was made using the bead mill under the above conditions to obtain [Pigment-wax dispersion 4]. The solids concentration of [Pigment-wax dispersion 4] was 50%.

[0201] Comparative Example 3 [Toner 8] was obtained in the same manner as in Example 1, except that the conditions for dispersing carbon black and wax in the <Preparation of oil layer> step were changed to a liquid sending speed of 1 kg / hour, disk peripheral speed of 6 m / second, 0.5 mm zirconia beads filled at 80% by volume, and 10 passes. The physical properties of the obtained [Toner 8] are shown in Table 1, and the evaluation results are shown in Table 2.

[0202] Comparative Example 4 [Toner 9] was obtained in the same manner as in Example 1, except that the conditions for dispersing carbon black and wax in the <Preparation of oil layer> step were changed to a liquid sending speed of 1 kg / hour, disk peripheral speed of 6 m / second, 0.5 mm zirconia beads filled at 80% by volume, and one pass. The physical properties of the obtained [Toner 9] are shown in Table 1, and the evaluation results are shown in Table 2.

[0203] Example 6 [Toner 10] was obtained in the same manner as in Example 1, except that the amount of [Pigment-Wax Dispersion 1] used in the <emulsification> step was changed from 749 parts to 1,250 parts. The physical properties of the obtained [Toner 10] are shown in Table 1, and the evaluation results are shown in Table 2.

[0204] Example 7 [Toner 11] was obtained in the same manner as in Example 1, except that the amount of [Pigment-Wax Dispersion 1] used in the <emulsification> step was changed from 749 parts to 1,500 parts. The physical properties of the obtained [Toner 11] are shown in Table 1, and the evaluation results are shown in Table 2.

[0205] Example 8 [Toner 12] was obtained in the same manner as in Example 1, except that the conditions for stirring the reaction materials in the reaction vessel in the process of <Preparation of Vinyl Resin Dispersion 1> in Example 1 were changed from 3,800 rpm for 30 minutes to 3,200 rpm for 30 minutes. The physical properties of the obtained [Toner 12] are shown in Table 1, and the evaluation results are shown in Table 2.

[0206] Example 9 [Toner 13] was obtained in the same manner as in Example 1, except that the conditions for stirring the reaction materials in the reaction vessel in the process of <Preparation of Vinyl Resin Dispersion 1> in Example 1 were changed from 3,800 rpm for 30 minutes to 4,300 rpm for 30 minutes. The physical properties of the obtained [Toner 13] are shown in Table 1, and the evaluation results are shown in Table 2.

[0207] The prepared [Toner 1] to [Toner 13] were evaluated as follows. In the following evaluations, the evaluation machine used was "Evaluation Machine A" described below.

[0208] <<Evaluation Machine A>> The evaluation machine A was a RICOH imagio MP C5002 with modified development and fixing units. The development unit, transfer unit, cleaning unit, and transport unit were all changed or adjusted so that the linear speed was 400 mm / s. The development gap was 1.26 mm, the doctor blade gap was 1.6 mm, and the reflective photosensor function was turned off. The fixing unit of the fixing unit was also adjusted with a fixing surface pressure of 1.0 x 10 4 The fixing nip width was 10 mm and the surface of the fixing belt was coated with tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer resin (PFA), shaped, and surface-conditioned. The fixing belt was a member having a conductive layer (average thickness 200 μm) between the base layer and the surface layer. The actual temperature range of the photoconductor section, the developing device section, and the transfer device section was controlled to be 30°C to 45°C (see Figure 2A).

[0209] <Evaluation items>

[0210] (1) Wax content in toner (total amount) The wax content in each toner was calculated from the endothermic heat of the wax obtained from each sample using the following formula 1, with the following measuring device and measuring conditions, using each toner sample and the following single wax sample as the measurement sample. Note that the measurement was performed once, and the endothermic heat of the wax was obtained from the DSC curve at the second temperature rise. [Measurement equipment and conditions] Measurement equipment: DSC equipment (DSC60, manufactured by Shimadzu Corporation) Sample size: Approx. 5 mg Heating temperature: 10℃ / min Measurement range: from room temperature to 150℃ Measurement environment: Nitrogen gas atmosphere Total amount of wax (mass%) = (amount of heat absorbed by the wax in the toner sample (J / g)) × 100) / (amount of heat absorbed by the wax sample alone (J / g)) Equation 1 Here, Nissan Elector (registered trademark) WEP-3 (manufactured by NOF Corporation), which is an ester wax, was used as the "single wax sample" in formula 1. The endothermic value of Nissan Elector (registered trademark) WEP-3 was 202.75 J / g.

[0211] (2) Relative amount of wax near the toner particle surface The relative amount of wax in the vicinity of the surface of each toner was measured using the following measuring device and under the following measuring conditions. As a sample, 3 g of each toner was pressed for 1 minute with a load of 6 t in an automatic pellet molding machine (Type M No. 50 BRP-E, manufactured by MAEKAWA TESTING MACHINE CO.) to prepare a pellet with a diameter of 40 mm (thickness of about 2 mm). The toner pellet was measured by the ATR method (total reflection method) using a Fourier transform infrared (FT-IR) spectroscopic analysis measuring device (Avatar370, manufactured by ThermoElectron). Peak 2,850 cm -1 (Height baseline 2,830cm -1 ~2,870cm -1 ) to P 2850 The peak height was 828cm. -1 (Baseline height 743cm -1 ~890cm -1 ) to P 828 The intensity ratio (P 2850 / P 828 ) was calculated. 2850 / P 828 ) was taken as the relative amount of wax near the surface of each toner.

[0212] (3) Average circularity of toner The average circularity of each toner was measured using the following measuring device and under the following measuring conditions. 0.1mL to 0.5mL of alkylbenzene sulfonate salt was added as a dispersant to 100mL to 150mL of water from which solid impurities had been removed in advance in a container, and then 0.1g to 0.5g of each toner sample was added as a measurement sample. The suspension in which each toner sample was dispersed was subjected to a dispersion treatment for about 1 minute to about 3 minutes using an ultrasonic disperser, and the shape and distribution of the toner were measured using a flow type particle image analyzer (FPIA-3000, manufactured by Toa Medical Electronics Co., Ltd.) with a dispersion concentration of 3,000 particles / μL to 10,000 particles / μL. In Table 1, "r 1 " indicates the long axis of the toner, and "r 2 " indicates the minor axis of the toner, and "r 3 " indicates the thickness of the toner, "r 3 / r 1 " is the thickness r 3 and minor axis r 2 It indicates the ratio of "r 3 / r 2 " is the thickness r 3 and minor axis r 2 The ratio is shown.

[0213] (4) Volume average particle size (Dv) and number average particle size (Dn) of toner The volume average particle size (Dv) and number average particle size (Dn) of each toner were measured using a precision particle size distribution measuring device (Multisizer 3, manufactured by Beckman Coulter, Inc.) From the obtained values, the particle size distribution (Dv / Dn) was calculated.

[0214] (5) Glass transition temperature (Tg) of toner The glass transition temperature (Tg) of each toner was measured using the DSC apparatus and under the measurement conditions described in (2) Wax Content in Toner. The Tg of the toner was determined from the DSC curve at the second temperature rise.

[0215] (6) Average thickness of toner shell layer The thickness of the shell layer of each toner was measured by the following method. After embedding the toner in an epoxy resin and hardening it, the toner was cut with a knife and an ultrathin section of the toner with a thickness of 80 nm was prepared using an ultramicrotome ULTRACUT UCT (Leica). The ultrathin section was then exposed to ruthenium tetroxide gas for 5 minutes to distinguish the shell and core. Furthermore, the ultrathin section of the toner was observed at an acceleration voltage of 100 kV using a TEM (transmission electron microscope) H7000 (Hitachi High-Tech Corporation) to measure the shell thickness. At this time, the shell thickness of 10 randomly measured toner particles was measured and the average value was calculated.

[0216] (7) Fixing properties (hot offset resistance and low-temperature fixing properties) Using the evaluation machine A and the two-component developer prepared using each toner, the transfer paper (Type 6200 (manufactured by Ricoh Co., Ltd.) and the copy printing paper) <135> (NBS Ricoh Co., Ltd.)) for a solid image, 1.0±0.1mg / cm 2 The fixing test was carried out by changing the temperature of the fixing belt, and the upper limit temperature at which no hot offset occurred on plain paper was taken as the upper limit fixing temperature. The lower limit fixing temperature was also measured on thick paper. The minimum fixing temperature is the fixing roller temperature at which the residual image density of the fixed image after rubbing with a pad is 70% or more, assuming that the image density of the fixed image is 100%. The maximum fixing temperature is preferably 200°C or more, and the minimum fixing temperature is preferably 140°C or less.

[0217] (8) Charge stability Using the evaluation machine A and the two-component developer prepared using each toner, a durability test was conducted by continuously outputting 100,000 sheets of a chart with an image area ratio of 5%, and the change in the charge amount at that time was evaluated. 1 g of the developer was weighed, and the change in the charge amount was obtained by the blow-off method, and evaluated according to the following evaluation criteria. - Evaluation criteria for charging stability - ◯: The change in charge amount is 5 μc / g or less. △: The change in charge amount exceeds 5 μc / g and is 10 μc / g or less. ×: The change in charge amount exceeds 10 μc / g.

[0218] (9) Image Density Using the evaluation machine A and a two-component developer prepared using each toner, a toner density of 0.4±0.1 mg / cm was measured on plain paper (Type 6200, Ricoh Co., Ltd.). 2 After outputting a solid image with the amount of toner attached, the image density was measured using an X-Rite (manufactured by X-Rite Corporation) and evaluated according to the following evaluation criteria. -Evaluation criteria for image density- ◯: Image density is 1.4 or more. ×: Image density is less than 1.4.

[0219] (10) Coverage In an environment of 10°C temperature and 15% relative humidity, a durability test was conducted by continuously outputting 100,000 sheets of a chart with an image area ratio of 5% using evaluation machine A and a two-component developer prepared using each toner. After that, the degree of toner staining on the background of the transfer paper was observed visually (with a magnifying glass) and evaluated according to the following evaluation criteria. -Fog evaluation criteria- ⊚: Good condition with absolutely no toner staining observed. ○: Slight dirt is observed but not problematic. △: A little dirt is observed. ×: Very dirty and problematic condition outside the acceptable range.

[0220] (11) Toner scattering In an environment of 40°C temperature and 90% relative humidity, a durability test was conducted by continuously outputting 100,000 sheets of a chart with an image area ratio of 5% using evaluation machine A and a two-component developer prepared using each toner. After that, the state of toner contamination inside the copier was visually observed and evaluated according to the following evaluation criteria. -Fog evaluation criteria- ⊚: No toner stains were observed and the condition was good. ○: Slight dirt is observed but not problematic. △: A little dirt is observed. ×: Very dirty and problematic condition outside the acceptable range.

[0221] (12) Environmental preservation (blocking resistance) 10g of each toner was weighed out and placed in a 20ml glass container, the glass bottle was tapped 100 times, and then the toner was left in a thermostatic chamber set at high temperature and high humidity (temperature 55°C, relative humidity 80%) for 24 hours, after which the penetration was measured with a penetrometer. 10g of each toner was weighed out and placed in a 20ml glass container, the glass bottle was tapped 100 times, and then the toner was stored in a low temperature and low humidity environment (temperature 10°C, relative humidity 15%) for 24 hours, and the penetration was measured in the same manner. The smaller penetration value between the high temperature and high humidity environment and the low temperature and low humidity environment was used and evaluated according to the following evaluation criteria. -Evaluation criteria for environmental preservation (blocking resistance)- ◎: Penetration is 20mm or more. ○: Needle penetration is 15mm or more but less than 20mm. △: Needle penetration is 10mm or more and less than 15mm. ×: Penetration is less than 10 mm.

[0222] (13) Fixed stains Using evaluation machine A and a two-component developer prepared using each toner, 10,000 charts with an image area ratio of 5% were continuously output, and the state in which trace amounts of offset matter adhering to the fixing belt were re-adhered onto the paper was visually observed, and evaluated according to the following evaluation criteria. - Evaluation criteria for fixed stains - ○: No stains detected at all. △: One or two stains were detected per sheet. ×: The stains are so severe that it cannot be used.

[0223] (14) Abnormal noises Using evaluation machine A and a two-component developer prepared using each toner, 10,000 sheets were output continuously, and the occurrence of abnormal noise was confirmed between 9,991 sheets and 10,000 sheets. -Evaluation criteria for abnormal noise generation- ○: No abnormal noise at all. △: There is a slight noise, but it's not annoying. ×: Abnormal noise occurs.

[0224] The physical properties of the toners obtained in Examples 1 to 9 and Comparative Examples 1 to 4 are shown in Table 1 below, and the evaluation results of each toner are shown in Table 2 below.

[0225] [Table 1]

[0226] [Table 2]

[0227] As can be seen from the results in Tables 1 and 2, by using a toner in which the wax content in the toner and the relative amount of wax near the toner particle surface measured by the FTIR-ATR method are within a specific range in a fixing device having a heater that heats the toner image in the nip portion, it is possible to obtain a toner with a low minimum fixing temperature and excellent low-temperature fixing property, a high maximum fixing temperature and excellent hot offset resistance, good environmental storage stability, and excellent charging properties, developability, and transferability, and to suppress the generation of abnormal noise. In addition, by controlling the circularity, shape, and particle size, there is no fogging or toner scattering, and cleaning properties are also good.

[0228] The aspects of the present invention include, for example, the following. <1> 1. An image fixing method for fixing a toner image formed on a recording medium by an image fixing device, comprising: the toner contains a wax and a binder resin, and contains toner particles having a core-shell structure having a core portion and a shell layer; the content of the wax in the toner is 3% by mass to 10% by mass, Peak (2,850 cm) determined by FTIR-ATR (attenuated total reflection infrared spectroscopy) -1 ) and peak (828cm -1 ) and the intensity ratio (P 2850 / P 828 ) is greater than or equal to 0.05 and less than or equal to 0.40, the image fixing device includes a pressure means, a driving means for driving and rotating the pressure means, a fixing means arranged opposite to the pressure means so as to come into contact with the pressure means to form a nip portion and rotated with the rotation of the pressure means, and a heater for heating the fixing means; The image fixing method further comprises a heating step of heating the toner image by the fixing means in the nip portion. <2> The toner has a wax content of 3% by mass to 5% by mass. <1> The image fixing method is as described in the above. <3> The wax is an ester wax. <1> from <2> 13. The image fixing method according to claim 12, wherein the image fixing step is carried out in a manner similar to that described above. <4> The shell layer has an average thickness of 200 nm to 400 nm. <1> from <3> 13. The image fixing method according to claim 12, wherein the image fixing step is carried out in a manner similar to that described above. <5> The heater is a plate heater. <1> from <4> 13. The image fixing method according to claim 12, wherein the image fixing step is carried out in a manner similar to that described above. <6> The surface pressure of the plate heater is 1.5×10 5 The above-mentioned <5> The image fixing method is as described in the above. <7> An image fixing device for fixing a toner image formed on a recording medium using a toner, the toner contains a wax and a binder resin, and contains toner particles having a core-shell structure having a core portion and a shell layer; the content of the wax in the toner is 3% by mass to 10% by mass, Peak (2,850 cm) determined by FTIR-ATR (attenuated total reflection infrared spectroscopy) -1 ) and peak (828cm -1 ) and the intensity ratio (P 2850 / P 828 ) is greater than or equal to 0.05 and less than or equal to 0.40, the image fixing device includes a pressure means, a driving means for driving and rotating the pressure means, a fixing means arranged opposite to the pressure means so as to come into contact with the pressure means to form a nip portion and rotated with the rotation of the pressure means, and a heater for heating the fixing means; The fixing unit heats the toner image in the nip portion. The image forming apparatus is characterized in that: <8> An electrostatic latent image carrier; an electrostatic latent image forming means for forming an electrostatic latent image on the electrostatic latent image bearing member; a developing means for developing the electrostatic latent image with a developer containing a toner to form a visible image; a transfer means for transferring the visible image onto a recording medium; an image fixing device for fixing the transferred image on the recording medium; having the toner contains a wax and a binder resin, and contains toner particles having a core-shell structure having a core portion and a shell layer; the content of the wax in the toner is 3% by mass to 10% by mass, Peak (2,850 cm) determined by FTIR-ATR (attenuated total reflection infrared spectroscopy) -1 ) and peak (828cm -1 ) and the intensity ratio (P 2850 / P 828 ) is greater than or equal to 0.05 and less than or equal to 0.40, the image fixing device includes a pressure means, a driving means for driving and rotating the pressure means, a fixing means arranged opposite to the pressure means so as to come into contact with the pressure means to form a nip portion and rotated with the rotation of the pressure means, and a heater for heating the fixing means; The fixing unit heats the toner image in the nip portion. The image forming apparatus is characterized in that: <9> an electrostatic latent image forming step of forming an electrostatic latent image on an electrostatic latent image carrier; a developing step of developing the electrostatic latent image with a developer containing a toner to form a visible image; a transfer step of transferring the visible image onto a recording medium; a fixing step of fixing the transferred image on the recording medium by an image fixing device; Including, the toner contains a wax and a binder resin, and contains toner particles having a core-shell structure having a core portion and a shell layer; the content of the wax in the toner is 3% by mass to 10% by mass, Peak (2,850 cm) determined by FTIR-ATR (attenuated total reflection infrared spectroscopy) -1 ) and peak (828cm -1 ) and the intensity ratio (P 2850 / P 828 ) is greater than or equal to 0.05 and less than or equal to 0.40, the image fixing device includes a pressure means, a driving means for driving and rotating the pressure means, a fixing means arranged opposite to the pressure means so as to come into contact with the pressure means to form a nip portion and rotated with the rotation of the pressure means, and a heater for heating the fixing means; The image forming method further comprises a heating step of heating the toner image by the fixing means in the nip portion.

[0229] The above <1> from <6> The image fixing method according to any one of the preceding claims. <7> The image fixing device according to the <8> and the image forming apparatus according to the above. <9> According to the image forming method described in the above, the conventional problems can be solved and the object of the present invention can be achieved. [Explanation of symbols]

[0230] x x-axis in toner y y-axis in toner z z-axis of toner r 1 Long axis of toner r 2 Toner minor axis r 3 Toner Thickness 109 Image fixing device 1020 Fixing belt 1021 Pressure roller 1021a Core metal 1021b Elastic layer 1021c Release layer 1022 Heater 1023 Heater Folder 1023a Protrusion 1024 Stay 1025 Thermistor 1026 Guide part 1030 Base material 1031 Resistance heating element 1032 Insulating layer 1260 Belt facing surface 1044 Pressure roller 1045 Nip forming member 1046 Pressure Belt 1047 Stay P Recording medium N Fixing nip area N1 Heating nip (first fixing nip area) N2 heated nip (second fusing nip area) 20 Developer 21 Developing sleeve 22 Power supply 23 Development section 24 Photoconductor drum 31 Photoreceptor 32 Charging roller 33 Core wire 34 Conductive rubber layer 35 Power supply 41 Photoreceptor 42 Brush roller 43 Core 44 Brush section 45 Power supply [Prior art documents] [Patent documents]

[0231] [Patent Document 1] JP 2007-249082 A

Claims

1. 1. An image fixing method for fixing a toner image formed on a recording medium by an image fixing device, comprising: the toner contains a wax and a binder resin, and contains toner particles having a core-shell structure having a core portion and a shell layer; the content of the wax in the toner is 3% by mass to 10% by mass, Peak determined by FTIR-ATR (attenuated total reflection infrared spectroscopy) method (2,850 cm -1 ) and Peak (828 cm -1 ) and the intensity ratio (P 2850 / P 828 ) is equal to or greater than 0.05 and equal to or less than 0.40; the image fixing device includes a pressure means, a driving means for driving and rotating the pressure means, a fixing means arranged opposite to the pressure means so as to come into contact with the pressure means to form a nip portion and rotated with the rotation of the pressure means, and a plate heater for heating the nip portion of the fixing means; The image fixing method further comprises a heating step of heating the toner image by the fixing means in the nip portion.

2. 2. The image fixing method according to claim 1, wherein the content of the wax in the toner is 3% by mass to 5% by mass.

3. 3. The image fixing method according to claim 1, wherein the wax is an ester wax.

4. 4. The image fixing method according to claim 1, wherein the shell layer has an average thickness of 200 nm to 400 nm.

5. An image fixing method described in any one of claims 1 to 4, wherein the fixing means has a cylindrical substrate and an endless fixing film arranged on the surface of the cylindrical substrate.

6. The surface pressure of the plate heater is 1.5×10 5 6. The image fixing method according to claim 1, wherein the viscosity is 0.1 Pa or less.

7. An electrostatic latent image carrier; an electrostatic latent image forming means for forming an electrostatic latent image on the electrostatic latent image bearing member; a developing means for developing the electrostatic latent image with a developer containing a toner to form a toner image; a transfer means for transferring the toner image onto a recording medium; an image fixing device that fixes the toner image transferred onto the recording medium; having the toner contains a wax and a binder resin, and contains toner particles having a core-shell structure having a core portion and a shell layer; the content of the wax in the toner is 3% by mass to 10% by mass, Peak determined by FTIR-ATR (attenuated total reflection infrared spectroscopy) method (2,850 cm -1 ) and Peak (828 cm -1 ) and the intensity ratio (P 2850 / P 828 ) is equal to or greater than 0.05 and equal to or less than 0.40; the image fixing device includes a pressure means, a driving means for driving and rotating the pressure means, a fixing means arranged opposite to the pressure means so as to come into contact with the pressure means to form a nip portion and rotated with the rotation of the pressure means, and a plate heater for heating the nip portion of the fixing means; The fixing unit heats the toner image in the nip portion.

1. An image forming apparatus comprising:

Citation Information

Patent Citations

  • Toner, developer, image forming apparatus, process cartridge, and image forming method

    JP2004246345A

  • Image forming apparatus

    JP2007079086A

  • Toner for developing electrostatic charge image, its manufacturing method, image forming apparatus, and processing cartridge

    JP2007249082A

  • Electrostatic charge image developing toner, developer, toner-containing container, and process cartridge

    JP2011118128A

  • Fixing method, image forming method, and image forming apparatus

    JP2019139226A